Linking multidimensional cropland ecosystem health assessment, spatialized dominant-driver diagnosis and mechanism-informed zoning in the middle and lower Yellow River, China - Shanshan Guo; Peter M. Atkinson; Junchang Huang; Hejie Wei; Tingyuan Zhou; Ling Li (Agricultural Systems, 2026)

Phylogenomic analyses reveal introgression and cryptic speciation in the globally distributed, vector-transmitted pathogen Plasmodium relictum - Esther Weyer; Angela N. Theodosopoulos; Vaidas Palinauskas; Staffan Bensch; Helena Westerdahl; Mélanie Duc; Arif Ciloglu; Xi Huang; Kyeong Soon Kim; Yoshio Tsuda; Carter T. Atkinson; Pavel Zehtindjiev; et al. (Molecular Phylogenetics and Evolution, 2026)

Comparative Effects of Thermal Recovery Strategies on Strength, Muscle Soreness and Molecular Markers Following Exercise-Induced Muscle Damage in Healthy Adults - F. Bayne; M. Nagyova; N. Stolk; M.A. Placido; M. Hamdi; A. Falzon; R. Perezen; S. Neto Menezes; S. Haliti; C. Atkinson; S. Racinais; N. Gaoua (Journal of Thermal Biology, 2026)

UTCMapper for 0.3 m urban tree canopy mapping: A case study in Shanghai - Shuang Zhang; Qunming Wang; Qiquan Yang; Xiaohua Tong; Peter M. Atkinson (Remote Sensing of Environment, 2026)

Unveiling small-scale tropical forest loss and post-loss recovery in the Congo Basin - Yihang Zhang; Xiaodong Li; Feng Ling; Xia Wang; Yun Du; Peter M. Atkinson (Global Environmental Change, 2026)

Body Size, Dispersal Potential, Range Size and Habitat Fragmentation Are Linked to Extinction Risk of Freshwater Mussels - Garrett W. Hopper; Sean M. Keogh; Carla L. Atkinson; Traci P. DuBose; Jeffrey D. Lozier; John M. Pfeiffer; Irene Sánchez González (Journal of Biogeography, 2026)
Aim Trait‐based approaches are increasingly recognised as tools for understanding species' vulnerabilities to intensifying global change. For species with complex life histories that involve a parasitic life stage, a combination of traits associated with either the host or parasite could influence extinction risk. Location United States of America. Taxon Freshwater mussels are a highly threatened assemblage of bivalves with an obligate ectoparasitic larval stage requiring a host fish. Adult mussels are sedentary, with long‐distance dispersal dictated by the dispersal ability of the host fish during the parasitic larval life phase. Methods We integrate several open‐source spatial and trait datasets for freshwater mussels and host fishes to test hypotheses about the relationship between species‐level traits such as body size, area of occupancy (AOO), host fish dispersal, habitat fragmentation and mussel extinction risk. Results Imperilled mussels were smaller, had smaller areas of occupancy, used small‐bodied, dispersal‐limited host fishes and had higher densities of large dams in their AOO compared to non‐imperilled mussels. Conclusions Body size, along with AOO and dispersal potential, appears to have cascading effects on imperilment where decreases in these traits potentiate population fragmentation via large dams. Thus, in contrast to many other groups, freshwater mussel body size is inversely related to extinction risk, and small‐bodied mussels should be closely monitored to prevent future extinctions.

The dynamic response of vegetation water use efficiency to wildfire disturbances in the Northern Hemisphere - Huipeng Xi; Qunming Wang; Peter M. Atkinson (Agricultural and Forest Meteorology, 2026)

Contemporary Methods for Capturing Juvenile Salmonids in the Marine Environment - Sean C. Godwin; Emma M. Atkinson; Jamieson B. Atkinson; Mackenzie C. Bartlett; William D. P. Duguid; Marc Trudel; Andrew W. Bateman (Fish and Fisheries, 2026)
Anadromous salmonids play vital roles in marine and freshwater ecosystems. The most abundant of these fishes—Pacific salmon ( Oncorhynchus spp.)—are integral to coastal ecosystems and communities across the North Pacific Rim, but numerous populations are experiencing dramatic declines, particularly towards the south of their range. Although many declines have been linked to poor marine survival, the early marine life phase of salmon has historically been difficult to study because of challenges in capturing juvenile salmon once they leave freshwater. Recent advancements in capture methods, refined over decades of research, have greatly expanded our understanding of juvenile Pacific salmon life history. Here, we synthesise and review the literature on the five main capture techniques for juvenile Pacific salmon in the marine environment: beach seine, miniature purse seine, conventional purse seine, microtroll, and rope trawl. We compare gear, selectivity, cost, and fish welfare considerations across methods. Along with demonstrated utility in Pacific salmon research, these methods also have broad—and in some cases unexplored—applicability for studying other salmonids and nearshore marine fishes globally, including invasive populations and Atlantic salmon.

Crowd detection using Very-Fine-Resolution satellite imagery - Tong Xiao; Qunming Wang; Ping Lu; Tenghai Huang; Xiaohua Tong; Peter M. Atkinson (ISPRS Journal of Photogrammetry and Remote Sensing, 2026)

Diarrhoea in children under 5 years in two informal settlements in Accra, Ghana: The impact of antecedent rainfall and flooding - Mehmet A. Veral; Manoj Roy; Roger W. Pickup; Richard Bayitse; Pat M. Agbedor; Mark Akrong; Peter M. Atkinson (Environmental Research, 2026)

Echocardiographic predictors of persistent left heart enlargement in dogs undergoing surgical mitral valve repair - B.K. Atkinson; M. Rossanese; D.J. Brockman; V. Luis Fuentes (Journal of Veterinary Cardiology, 2026)

Activation of the alternative complement pathway and its relevance for sodium retention in experimental nephrotic syndrome - Daniel Essigke; M. Zaher Kalo; Lingsi Kong; Matthias Wörn; Mohammad-Khaled Saad; Kingsley Omage; Bernhard N. Bohnert; Andreas L. Birkenfeld; John P. Atkinson; Xiaobo Wu; Ferruh Artunc (Pflügers Archiv - European Journal of Physiology, 2026)
The complement component C3, factor B (FB) and factor D (FD) belong to the alternative complement pathway and have been identified in urine samples from nephrotic mice. However, it is not yet known whether these factors are involved in mediating sodium retention in nephrotic syndrome (NS). Here we used a genetic mouse model of NS based on an inducible podocin deletion ( Nphs2 Δipod ). These mice were intercrossed with mice deficient for FB, FD or C3, yielding Nphs2 Δipod *Cfb −/− , Nphs2 Δipod *Cfd −/− or Nphs2 Δipod *C3 −/− mice, respectively. NS was induced after oral doxycycline treatment for 14 days. C3, FB and FD were detected in the nephrotic urine of Nphs2 Δipod mice as well as fragments of C3 and FB, indicating intrarenal activation of the alternative complement pathway. Lack of FB and FD had no impact on the activation of C3. Immunohistochemistry demonstrated positive C3 staining in protein casts and within the proximal tubule. Nephrotic mice of all genotypes experienced similar proteolytic activation of the epithelial sodium channel ENaC, developed sodium retention (urinary sodium concentration < 20 mM) and body weight gain. This was associated with a stimulation of proteolytic processing of epithelial sodium channel ENaC in all genotypes. In conclusion, components of the alternative complement pathway are detectable and activated in nephrotic syndrome. Mice with deletion of C3, FB or FD are not protected from proteolytic ENaC activation and sodium retention in NS.

Genomic Architecture of Inbreeding Depression Associated With Hatching Failure in an Endangered Parrot - Yasmin Foster; Stefanie Grosser; Brodie J. Foster; Nicolas Dussex; Aimee Stubbs; Ludovic Dutoit; Theo Atkinson; Fiona Robertson; Ken G. Dodds; Rudiger Brauning; Jeanne M. E. Jacobs; John C. McEwan; et al. (Molecular Ecology, 2026)
Conservation management of endangered species increasingly relies on genomic approaches to understand how long‐term small population sizes affect the fitness of extant individuals. However, despite the growing investment in genomic resources by conservation programmes, the impact that sequencing methods have on the ability to detect inbreeding‐related phenomena has been largely overlooked. Here, we compare the use of whole‐genome and reduced‐representation sequencing approaches in 148 individuals of the critically endangered parrot, the kākāpō ( Strigops habroptilus ), to assess inbreeding and its effects on female reproductive success. We explore how sequencing choice influences the identification of long stretches of homozygosity across the genome (runs of homozygosity, ROH), and compare the conservation implications of the results produced by each method. Both whole‐genome and reduced‐representation sequencing approaches provided comparable estimates of genome‐wide inbreeding ( F ROH ) and revealed consistent effects on egg hatching success, suggesting that reduced‐representation sequencing is capable of detecting inbreeding depression in wild populations under certain conditions. Whole‐genome sequencing enabled chromosome‐level inbreeding analyses, which revealed no strong evidence of chromosome‐specific effects beyond the genome‐wide signal. These results suggest that inbreeding depression in kākāpō reflects small effects across many chromosomes rather than strong effects on only a few, and that the primary benefit of whole‐genome sequencing lies in improving the precision of genome‐wide inbreeding estimates rather than identifying chromosome‐specific effects. Our findings highlight the distinct benefits of each sequencing approach in conservation, particularly within the context of resource limitations.

An assessment model for linking changes in pelagic habitat state to impacts on human wellbeing - Matthew P. Faith; Siân E. Rees; Angus Atkinson; Mike Best; Eileen Bresnan; Michelle J. Devlin; Matthew M. Holland; Holly J. Niner; Clare Ostle; Paul Tett; Abigail McQuatters-Gollop (Marine Policy, 2025)

Integrated modeling for evaluating microbial pollution in an urban freshwater coastal river - Angshuman M. Saharia; Zhenduo Zhu; Joseph F. Atkinson (Journal of Hydrology, 2025)

Establishing a Historical Fine-Resolution Urban Database from KH-9 HEXAGON MCS and PCS Imagery Including an Urban Landscape Map, Stereo Anaglyph Image and Digital Surface Model - AmirReza Shahtahmassebi; Golnaz Shahtahmassebi; Nathan Moore; Peter M. Atkinson (PFG – Journal of Photogrammetry, Remote Sensing and Geoinformation Science, 2025)

The Scale and Distribution of Microplastic Pollution in the Soils of a UK Urban Woodland - Faye M. Weaver; Neil L. Rose; Simon D. Turner; Bonnie Atkinson (Water, Air, & Soil Pollution, 2025)

A global meta‐analysis of ecological functions and regulating ecosystem services of freshwater bivalves - Alexandra Zieritz; Joshua I. Brian; Ronaldo Sousa; David C. Aldridge; Carla L. Atkinson; Karel Douda; Caryn Vaughn; Yulia Bespalaya; Tabitha Richmond; Adam M. Ćmiel; Alma Crisp; Andreas H. Dobler; et al. (Limnology and Oceanography, 2025)
Freshwater bivalves are globally distributed, diverse, and common in benthic communities. Many taxa, particularly in the most species‐rich order, Unionida, are declining due to anthropogenic stressors, while a small number of non‐native species have become increasingly abundant and widespread, commonly replacing native bivalve assemblages. To understand how these global changes may impact ecosystems and people, we conducted a meta‐analysis of existing literature quantifying the ecological functions (= supporting or intermediate ecosystem services) and regulating ecosystem services of freshwater bivalves (hereafter “ecosystem services”). Random effects meta‐analysis modeling across 447 case studies revealed a positive effect on human health, safety, or comfort of freshwater bivalve ecosystem services overall and specifically, via effects on native macrofauna, microorganisms, wastes, and pollutants, and the physico‐chemical condition or quantity of sediments. Generally, effects of native species and species within the orders Unionida and Venerida were more significant and positive than those of other freshwater bivalves. No significant overall effect was found for ecosystem services related to zooplankton, algae, invasive species, and the physico‐chemical condition of ambient water. Moreover, a significant bias toward publication of positive results existed for studies quantifying ecosystem services related to algae. These findings illustrate the global importance of the ecosystem services of freshwater bivalves and highlight the need for large‐scale conservation and restoration efforts for their species and populations globally, including those of common species. Our findings also question common assumptions of strong and ubiquitous effects of freshwater bivalves on algae and water condition, cautioning against extrapolating observations across systems.

A role for dendroecology in guiding hydrologic restoration and mitigating risks of peatland soil loss: an example from Chamaecyparis thyoides forests - Robert B. Atkinson; Abigail Weaver; Joshua A. Kincaid; Frederic C. Wurster; James M. B. Doyle (Trees, 2025)
Key message Tree rings of Chamaecyparis thyoides exhibit growth responses that are influenced by local hydrologic conditions through decadal timescales. That perspective can assist peatland natural resource managers in selection of hydrologic restoration targets that minimize chronic microbial oxidation and acute peat loss associated with fire. Abstract Temperate forested peatlands are valued for myriad ecosystem services including carbon storage and biodiversity which may be lost through anthropogenic disturbance of hydrologic regimes. Hydrologic alterations may be recorded in tree stem growth patterns and provide insights for management and restoration. In Chamaecyparis thyoides (Atlantic White Cedar, Juniper) swamps, stand drainage causes a shift from net soil carbon sink to source as microbial oxidation and catastrophic fire oxidize stored organic matter. Here, we analyze historic radial growth patterns in C. thyoides in order to characterize drainage history to guide hydrologic management for peat conservation and restoration. Basal area increment (BAI) estimates across a ~ 60-year chronology (1939–2003) were analyzed by flexible beta cluster analysis of 185 trees from 13 C. thyoides stands in the Great Dismal Swamp National Wildlife Refuge in Virginia and North Carolina, USA. Stands formed 3 groups, and growth rates among all groups were indicative of a drained hydrologic regime throughout the chronology compared to an undrained control stand. Regime shift analyses identified positive shifts for 2 stand groups in 1954 and for all 3 stand groups in 1963. Multiple response permutation procedures and partial mantel tests both identified two predictive growth variables including (1) visual observations of fluctuation in the water table and (2) proximity to a primary ditch. Growth rate was suppressed when weirs were installed in the mid-1980s; however, growth rebounded within ~ 2 years. The chronology ends when stands were struck by a major hurricane in 2003 and fires in 2008 and 2011 liberated 1.38 Tg of peat carbon. We conclude that dendroecology can detect hydrologic changes through time and can reduce risks of microbial oxidation and catastrophic fire in forested peatlands.

Pace of alcohol drinking during in natural-environment drinking is associated with heightened alcohol-related reward and negative consequences in risky drinkers - Emily A. Atkinson; Andrew M. Fischer; John F. Cursio; Andrea C. King; Daniel J. Fridberg (Psychopharmacology, 2025)

The winds of change? Attitudes toward wind projects and their electoral implications in Texas - Talbot M. Andrews; Carol Atkinson-Palombo; Oksan Bayulgen; Adam Gallaher; Lyle Scruggs (Energy Policy, 2025)

European Breeding Bird Declines Associated With Narrower Climatic Niches - Karolina Zalewska; James J. Gilroy; Inês Catry; Philip W. Atkinson; Alena Klvaňová; Aldina M. A. Franco (Journal of Biogeography, 2025)
Aim Anthropogenic climate change has increasingly been identified as a major threat to global biodiversity. However, the extent of this threat is likely to be uneven across species, due to differences in life histories or exposure to environmental change. The range of climatic conditions a species experiences across its range extent, known as the realised climatic niche, may be an indicator of species resilience to climate change. Species with large range extents, occurring across diverse climatic conditions, are expected to be less affected by climate change due to lower physiological constraints and tolerance to a wider range of climates. However, this may not be the case if local populations are adapted to specific environmental conditions. In this study, we investigate whether the extent of the species' realised climatic niche, also known as the climatic niche breadth, is linked to their long‐term population trends. Location Europe. Taxon Birds. Methods We extract climate data across the breeding‐only and resident ranges of 159 European bird species and use an ordination method to produce a representation of the species climatic niches. We then relate the niche breadth of each species to their range area and incorporate this relationship, along with the species' diet, main habitat type, migratory status and average body mass, to investigate their relationship with the species long‐term population trend. Results Species with small range areas showed larger variation in climatic niche breadth than species with larger ranges. For species with similar range areas, those with broader climatic tolerance were less likely to be declining than those with narrow climatic niches. Main Conclusions These findings can help us understand the threats associated with climate change and allow for rapid assessment of the importance of climatic factors on population trends, providing an invaluable tool for targeting habitat conservation.

Worldwide Soundscapes: A Synthesis of Passive Acoustic Monitoring Across Realms - Kevin F. A. Darras; Rodney A. Rountree; Steven L. Van Wilgenburg; Anna F. Cord; Frederik Pitz; Youfang Chen; Lijun Dong; Agnès Rocquencourt; Camille Desjonquères; Patrick Mauritz Diaz; Tzu‐Hao Lin; Théophile Turco; et al. (Global Ecology and Biogeography, 2025)
Aim The urgency for remote, reliable and scalable biodiversity monitoring amidst mounting human pressures on ecosystems has sparked worldwide interest in Passive Acoustic Monitoring (PAM), which can track life underwater and on land. However, we lack a unified methodology to report this sampling effort and a comprehensive overview of PAM coverage to gauge its potential as a global research and monitoring tool. To address this gap, we created the Worldwide Soundscapes project, a collaborative network and growing database comprising metadata from 416 datasets across all realms (terrestrial, marine, freshwater and subterranean). Location Worldwide, 12,343 sites, all ecosystem types. Time Period 1991 to present. Major Taxa Studied All soniferous taxa. Methods We synthesise sampling coverage across spatial, temporal and ecological scales using metadata describing sampling locations, deployment schedules, focal taxa and audio recording parameters. We explore global trends in biological, anthropogenic and geophysical sounds based on 168 selected recordings from 12 ecosystems across all realms. Results Terrestrial sampling is spatially denser (46 sites per million square kilometre—Mkm 2 ) than aquatic sampling (0.3 and 1.8 sites/Mkm 2 in oceans and fresh water) with only two subterranean datasets. Although diel and lunar cycles are well sampled across realms, only marine datasets (55%) comprehensively sample all seasons. Across the 12 ecosystems selected for exploring global acoustic trends, biological sounds showed contrasting diel patterns across ecosystems, declined with distance from the Equator, and were negatively correlated with anthropogenic sounds. Main Conclusions PAM can inform macroecological studies as well as global conservation and phenology syntheses, but representation can be improved by expanding terrestrial taxonomic scope, sampling coverage in the high seas and subterranean ecosystems, and spatio‐temporal replication in freshwater habitats. Overall, this worldwide PAM network holds promise to support cross‐realm biodiversity research and monitoring efforts.

Mapping tropical dry Miombo woodlands into functional forest classes using Sentinel-1 and Sentinel-2 imagery and machine learning - Kennedy Kanja; Ce Zhang; Melvin Lippe; Peter M. Atkinson (Remote Sensing Applications: Society and Environment, 2025)

Mind the gap - The need to integrate novel plankton methods alongside ongoing long-term monitoring - Matthew M. Holland; Luis Felipe Artigas; Angus Atkinson; Mike Best; Eileen Bresnan; Michelle Devlin; Dafne Eerkes-Medrano; Marie Johansen; David G. Johns; Margarita Machairopoulou; Sophie Pitois; James Scott; et al. (Ocean & Coastal Management, 2025)

GLOSTFM: A global spatiotemporal fusion model integrating multi-source satellite observations to enhance land surface temperature resolution - Qingyan Meng; Shize Chen; Linlin Zhang; Xiaolin Zhu; Yeping Zhang; Peter M. Atkinson (Remote Sensing of Environment, 2025)

Unsupervised object-based spectral unmixing for subpixel mapping - Chengyuan Zhang; Qunming Wang; Peter M. Atkinson (Remote Sensing of Environment, 2025)

Data fidelity-oriented spatial-spectral fusion of CRISM and CTX images - Qunming Wang; Wenjing Ma; Sicong Liu; Xiaohua Tong; Peter M. Atkinson (ISPRS Journal of Photogrammetry and Remote Sensing, 2025)

Controls on regional sulphate distribution in shallow groundwater in the western Canadian Interior Plains - J.E. Liggett; K.E. Pooley; N. Atkinson; P. Humez; S. Thistle; B.D. Smerdon; M. Babakhani; C.N. McClain; B. Mayer (Science of The Total Environment, 2024)

Shorebirds Are Shrinking and Shape‐Shifting: Declining Body Size and Lengthening Bills in the Past Half‐Century - A. McQueen; M. Klaassen; G. J. Tattersall; S. Ryding; R. Atkinson; R. Jessop; C. J. Hassell; M. Christie; A. Fröhlich; M. R. E. Symonds (Ecology Letters, 2024)
Animals are predicted to shrink and shape‐shift as the climate warms, declining in size, while their appendages lengthen. Determining which types of species are undergoing these morphological changes, and why, is critical to understanding species responses to global change, including potential adaptation to climate warming. We examine body size and bill length changes in 25 shorebird species using extensive field data (> 200,000 observations) collected over 46 years (1975–2021) by community scientists. We show widespread body size declines over time, and after short‐term exposure to warmer summers. Meanwhile, shorebird bills are lengthening over time but shorten after hot summers. Shrinking and shape‐shifting patterns are consistent across ecologically diverse shorebirds from tropical and temperate Australia, are more pronounced in smaller species and vary according to migration behaviour. These widespread morphological changes could be explained by multiple drivers, including adaptive and maladaptive responses to nutritional stress, or by thermal adaptation to climate warming.

Predictors of long-term variability in NE Atlantic plankton communities - Matthew M. Holland; Angus Atkinson; Mike Best; Eileen Bresnan; Michelle Devlin; Eric Goberville; Pierre Hélaouët; Margarita Machairopoulou; Matthew Faith; Murray S.A. Thompson; Abigail McQuatters-Gollop (Science of The Total Environment, 2024)

An efficient and generalisable approach for mapping paddy rice fields based on their unique spectra during the transplanting period leveraging the CIE colour space - Huapeng Li; Jujian Huang; Ce Zhang; Xiangyu Ning; Shuqing Zhang; Peter M. Atkinson (Remote Sensing of Environment, 2024)

Combination and summary of ATLAS dark matter searches interpreted in a 2HDM with a pseudo-scalar mediator using 139 fb−1 of s = 13 TeV pp collision data - G. Aad; B. Abbott; K. Abeling; N.J. Abicht; S.H. Abidi; A. Aboulhorma; H. Abramowicz; H. Abreu; Y. Abulaiti; A.C. Abusleme Hoffman; B.S. Acharya; C. Adam Bourdarios; et al. (Science Bulletin, 2024)

Identifying fine-scale archaeological features using KH-9 HEXAGON mapping and panoramic camera images: evidence from Liangzhu Ancient City - Amir Reza Shahtahmassebi; Golnaz Shahtahmassebi; Nathan Moore; Peter M. Atkinson (International Journal of Remote Sensing, 2024)

Ensembles of multiple models for soil moisture retrieval from remote sensing data over agricultural areas: A deep learning-based framework - Amir Sedighi; Saeid Hamzeh; Seyed Kazem Alavipanah; Abd Ali Naseri; Peter M. Atkinson (Remote Sensing Applications: Society and Environment, 2024)

Labrador Coastal Current and productivity variations offshore Nain (Nunatsiavut) during the late Holocene - M. Atkinson; A. Normandeau; N. Van Nieuwenhove; A. de Vernal; M. Saunders; J. Woollett; A. Limoges (Quaternary Science Reviews, 2024)

Mechanistic safety assessment via multi-omic characterisation of systemic pathway perturbations following in vivo MAT2A inhibition - Valentina Fogal; Filippos Michopoulos; Andrew F. Jarnuczak; Ghaith M. Hamza; Stephanie Harlfinger; Paul Davey; Heather Hulme; Stephen J. Atkinson; Piotr Gabrowski; Tony Cheung; Michael Grondine; Clare Hoover; et al. (Archives of Toxicology, 2024)
The tumour suppressor p16/CDKN2A and the metabolic gene, methyl-thio-adenosine phosphorylase (MTAP), are frequently co-deleted in some of the most aggressive and currently untreatable cancers. Cells with MTAP deletion are vulnerable to inhibition of the metabolic enzyme, methionine-adenosyl transferase 2A (MAT2A), and the protein arginine methyl transferase (PRMT5). This synthetic lethality has paved the way for the rapid development of drugs targeting the MAT2A/PRMT5 axis. MAT2A and its liver- and pancreas-specific isoform, MAT1A, generate the universal methyl donor S-adenosylmethionine (SAM) from ATP and methionine. Given the pleiotropic role SAM plays in methylation of diverse substrates, characterising the extent of SAM depletion and downstream perturbations following MAT2A/MAT1A inhibition (MATi) is critical for safety assessment. We have assessed in vivo target engagement and the resultant systemic phenotype using multi-omic tools to characterise response to a MAT2A inhibitor (AZ’9567). We observed significant SAM depletion and extensive methionine accumulation in the plasma, liver, brain and heart of treated rats, providing the first assessment of both global SAM depletion and evidence of hepatic MAT1A target engagement. An integrative analysis of multi-omic data from liver tissue identified broad perturbations in pathways covering one-carbon metabolism, trans-sulfuration and lipid metabolism. We infer that these pathway-wide perturbations represent adaptive responses to SAM depletion and confer a risk of oxidative stress, hepatic steatosis and an associated disturbance in plasma and cellular lipid homeostasis. The alterations also explain the dramatic increase in plasma and tissue methionine, which could be used as a safety and PD biomarker going forward to the clinic.

TSI-Siamnet: A Siamese network for cloud and shadow detection based on time-series cloudy images - Qunming Wang; Jiayi Li; Xiaohua Tong; Peter M. Atkinson (ISPRS Journal of Photogrammetry and Remote Sensing, 2024)

Determinants of host breadth in non-native bark and ambrosia beetles - Soňa Šenfeldová; Thomas H. Atkinson; Miloš Knížek; Robert J. Rabaglia; Nathan P. Havill; Samuel F. Ward; Marek Turčáni; Andrew M. Liebhold (Forest Ecology and Management, 2024)

Filling gaps in cloudy Landsat LST product by spatial-temporal fusion of multi-scale data - Qunming Wang; Yijie Tang; Xiaohua Tong; Peter M. Atkinson (Remote Sensing of Environment, 2024)

A novel surface energy balance-based approach to land surface temperature downscaling - Mohammad Karimi Firozjaei; Naeim Mijani; Majid Kiavarz; Si-Bo Duan; Peter M. Atkinson; Seyed Kazem Alavipanah (Remote Sensing of Environment, 2024)

Automatic mapping of 500 m daily open water body fraction in the American continent using GOES-16 ABI imagery - Xia Wang; Peter M. Atkinson; Yihang Zhang; Xiaodong Li; Kerong Zhang (Remote Sensing of Environment, 2024)

Observing change in pelagic animals as sampling methods shift: the case of Antarctic krill - Simeon L. Hill; Angus Atkinson; Javier A. Arata; Anna Belcher; Susan Bengtson Nash; Kim S. Bernard; Alison Cleary; John A. Conroy; Ryan Driscoll; Sophie Fielding; Hauke Flores; Jaume Forcada; et al. (Frontiers in Marine Science, 2024)
Understanding and managing the response of marine ecosystems to human pressures including climate change requires reliable large-scale and multi-decadal information on the state of key populations. These populations include the pelagic animals that support ecosystem services including carbon export and fisheries. The use of research vessels to collect information using scientific nets and acoustics is being replaced with technologies such as autonomous moorings, gliders, and meta-genetics. Paradoxically, these newer methods sample pelagic populations at ever-smaller spatial scales, and ecological change might go undetected in the time needed to build up large-scale, long time series. These global-scale issues are epitomised by Antarctic krill ( Euphausia superba ), which is concentrated in rapidly warming areas, exports substantial quantities of carbon and supports an expanding fishery, but opinion is divided on how resilient their stocks are to climatic change. Based on a workshop of 137 krill experts we identify the challenges of observing climate change impacts with shifting sampling methods and suggest three tractable solutions. These are to: improve overlap and calibration of new with traditional methods; improve communication to harmonise, link and scale up the capacity of new but localised sampling programs; and expand opportunities from other research platforms and data sources, including the fishing industry. Contrasting evidence for both change and stability in krill stocks illustrates how the risks of false negative and false positive diagnoses of change are related to the temporal and spatial scale of sampling. Given the uncertainty about how krill are responding to rapid warming we recommend a shift towards a fishery management approach that prioritises monitoring of stock status and can adapt to variability and change.

New insights into pesticide occurrence and multicompartmental monitoring strategies in stream ecosystems using periphyton and suspended sediment - Moira M. Ijzerman; Melanie Raby; Nicholas V. Letwin; Yaryna M. Kudla; Jenna D. Anderson; Brian J. Atkinson; Rebecca C. Rooney; Paul K. Sibley; Ryan S. Prosser (Science of The Total Environment, 2024)

Essential omega‐3 fatty acids are depleted in sea ice and pelagic algae of the Central Arctic Ocean - Katrin Schmidt; Martin Graeve; Clara J. M. Hoppe; Sinhué Torres‐Valdes; Nahid Welteke; Laura M. Whitmore; Philipp Anhaus; Angus Atkinson; Simon T. Belt; Tina Brenneis; Robert G. Campbell; Giulia Castellani; et al. (Global Change Biology, 2024)
Microalgae are the main source of the omega‐3 fatty acids eicosapentaenoic acid (EPA) and docosahexaenoic acid (DHA), essential for the healthy development of most marine and terrestrial fauna including humans. Inverse correlations of algal EPA and DHA proportions (% of total fatty acids) with temperature have led to suggestions of a warming‐induced decline in the global production of these biomolecules and an enhanced importance of high latitude organisms for their provision. The cold Arctic Ocean is a potential hotspot of EPA and DHA production, but consequences of global warming are unknown. Here, we combine a full‐seasonal EPA and DHA dataset from the Central Arctic Ocean (CAO), with results from 13 previous field studies and 32 cultured algal strains to examine five potential climate change effects; ice algae loss, community shifts, increase in light, nutrients, and temperature. The algal EPA and DHA proportions were lower in the ice‐covered CAO than in warmer peripheral shelf seas, which indicates that the paradigm of an inverse correlation of EPA and DHA proportions with temperature may not hold in the Arctic. We found no systematic differences in the summed EPA and DHA proportions of sea ice versus pelagic algae, and in diatoms versus non‐diatoms. Overall, the algal EPA and DHA proportions varied up to four‐fold seasonally and 10‐fold regionally, pointing to strong light and nutrient limitations in the CAO. Where these limitations ease in a warming Arctic, EPA and DHA proportions are likely to increase alongside increasing primary production, with nutritional benefits for a non‐ice‐associated food web.

Very fine spatial resolution urban land cover mapping using an explicable sub-pixel mapping network based on learnable spatial correlation - Da He; Qian Shi; Jingqian Xue; Peter M. Atkinson; Xiaoping Liu (Remote Sensing of Environment, 2023)

Spatio-temporal multi-level attention crop mapping method using time-series SAR imagery - Zhu Han; Ce Zhang; Lianru Gao; Zhiqiang Zeng; Bing Zhang; Peter M. Atkinson (ISPRS Journal of Photogrammetry and Remote Sensing, 2023)

Combining remote sensing and tracking data to quantify species' cumulative exposure to anthropogenic change - Claire Buchan; James J. Gilroy; Inês Catry; Chris M. Hewson; Philip W. Atkinson; Aldina M. A. Franco (Global Change Biology, 2023)
Identifying when and where organisms are exposed to anthropogenic change is crucial for diagnosing the drivers of biodiversity declines and implementing effective conservation measures. Accurately measuring individual‐scale exposure to anthropogenic impacts across the annual cycle as they move across continents requires an approach that is both spatially and temporally explicit—now achievable through recent parallel advances in remote‐sensing and individual tracking technologies. We combined 10 years of tracking data for a long‐distance migrant, (common cuckoo, Cuculus canorus ), with multi‐dimensional remote‐sensed spatial datasets encompassing thirteen relevant anthropogenic impacts (including infrastructure, hunting, habitat change, and climate change), to quantify mean hourly and total accumulated exposure of tracked individuals to anthropogenic change across each stage of the annual cycle. Although mean hourly exposure to anthropogenic change was greatest in the breeding stage, accumulated exposure to changes associated with direct mortality risks (e.g., built infrastructure) and with climate were greatest during the wintering stage, which comprised 63% of the annual cycle on average for tracked individuals. Exposure to anthropogenic change varied considerably within and between migratory flyways, but there were no clear between‐flyway differences in overall exposure during migration stages. However, more easterly autumn migratory routes were significantly associated with lower subsequent exposure to anthropogenic impacts in the winter stage. Cumulative change exposure was not significantly associated with recent local‐scale population trends in the breeding range, possibly because cuckoos from shared breeding areas may follow divergent migration routes and therefore encounter very different risk landscapes. Our study highlights the potential for the integration of tracking data and high‐resolution remote sensing to generate valuable and detailed new insights into the impacts of environmental change on wild species.

Major declines in NE Atlantic plankton contrast with more stable populations in the rapidly warming North Sea - Matthew M. Holland; Arnaud Louchart; Luis Felipe Artigas; Clare Ostle; Angus Atkinson; Isabelle Rombouts; Carolyn A. Graves; Michelle Devlin; Birgit Heyden; Margarita Machairopoulou; Eileen Bresnan; Jos Schilder; et al. (Science of The Total Environment, 2023)

Monitoring monthly tropical humid forest disturbances with Planet NICFI images in Cameroon - Yihang Zhang; Xia Wang; Xiaodong Li; Yun Du; Peter M. Atkinson (Agricultural and Forest Meteorology, 2023)

Relative sea‐level changes in southeastern Australia during the 19 th and 20 th centuries - S. L. Williams; E. Garrett; P. T. Moss; S. Dangendorf; F. D. Hibbert; N. R. Atkinson; V. Pashley; I. L. Millar; M. H. Garnett; A. Zawadzki; W. R. Gehrels (Journal of Quaternary Science, 2023)
Rates of global and regional sea‐level rise between ~1850 and 1950 were high compared to those in preceding centuries. The cause of this sea‐level acceleration remains uncertain, but it appears to be pronounced in a small set of relative sea‐level proxy records from the Southern Hemisphere. Here we generate three new proxy‐based relative sea‐level reconstructions for southeastern Australia to investigate spatial patterns and causes of historical sea‐level changes in the Tasman Sea. Palaeo sea‐level estimates were determined using salt‐marsh foraminifera as sea‐level indicators. Records are underpinned by chronologies based on accelerator mass spectrometry 14 C, radiogenic lead ( 210 Pb), stable lead isotopes and palynological analyses. Our reconstructions show that relative sea level rose by ~0.2–0.3 m over the last 200 years in southeastern Australia, and rates of sea‐level rise were especially high over the first half of the 20 th century. Based on modelled estimates of the contributing components to sea‐level rise, we suggest that the episode of rapid sea‐level rise was driven by barystatic contributions, but sterodynamic contributions were dominant by the mid‐20 th century. Significant spatial variability in relative sea level indicates that local to sub‐regional drivers of sea level are also prominent. Our reconstructions significantly enhance our understanding of the spatiotemporal pattern of early 20 th century sea‐level rise in the region.

Unpaired spatio-temporal fusion of image patches (USTFIP) from cloud covered images - Harkaitz Goyena; Unai Pérez-Goya; Manuel Montesino-SanMartin; Ana F. Militino; Qunming Wang; Peter M. Atkinson; M. Dolores Ugarte (Remote Sensing of Environment, 2023)

A novel Greenness and Water Content Composite Index (GWCCI) for soybean mapping from single remotely sensed multispectral images - Hui Chen; Huapeng Li; Zhao Liu; Ce Zhang; Shuqing Zhang; Peter M. Atkinson (Remote Sensing of Environment, 2023)

Zebrafish as a model for cardiac disease; Cryo-EM structure of native cardiac thin filaments from Danio Rerio - Marston Bradshaw; John M. Squire; Edward Morris; Georgia Atkinson; Rebecca Richardson; Jon Lees; Massimo Caputo; Giulia M. Bigotti; Danielle M. Paul (Journal of Muscle Research and Cell Motility, 2023)
Actin, tropomyosin and troponin, the proteins that comprise the contractile apparatus of the cardiac thin filament, are highly conserved across species. We have used cryo-EM to study the three-dimensional structure of the zebrafish cardiac thin and actin filaments. With 70% of human genes having an obvious zebrafish orthologue, and conservation of 85% of disease-causing genes, zebrafish are a good animal model for the study of human disease. Our structure of the zebrafish thin filament reveals the molecular interactions between the constituent proteins, showing that the fundamental organisation of the complex is the same as that reported in the human reconstituted thin filament. A reconstruction of zebrafish cardiac F-actin demonstrates no deviations from human cardiac actin over an extended length of 14 actin subunits. Modelling zebrafish homology models into our maps enabled us to compare, in detail, the similarity with human models. The structural similarities of troponin-T in particular, a region known to contain a hypertrophic cardiomyopathy ‘hotspot’, confirm the suitability of zebrafish to study these disease-causing mutations.

Retaining natural vegetation to safeguard biodiversity and humanity - Jeremy S. Simmonds; Andres Felipe Suarez‐Castro; April E. Reside; James E. M. Watson; James R. Allan; Scott C. Atkinson; Pasquale Borrelli; Nigel Dudley; Stephen Edwards; Richard A. Fuller; Edward T. Game; Simon Linke; et al. (Conservation Biology, 2023)
Global efforts to deliver internationally agreed goals to reduce carbon emissions, halt biodiversity loss, and retain essential ecosystem services have been poorly integrated. These goals rely in part on preserving natural (e.g., native, largely unmodified) and seminatural (e.g., low intensity or sustainable human use) forests, woodlands, and grasslands. To show how to unify these goals, we empirically derived spatially explicit, quantitative, area‐based targets for the retention of natural and seminatural (e.g., native) terrestrial vegetation worldwide. We used a 250‐m‐resolution map of natural and seminatural vegetation cover and, from this, selected areas identified under different international agreements as being important for achieving global biodiversity, carbon, soil, and water targets. At least 67 million km 2 of Earth's terrestrial vegetation (∼79% of the area of vegetation remaining) required retention to contribute to biodiversity, climate, soil, and freshwater conservation objectives under 4 United Nations’ resolutions. This equates to retaining natural and seminatural vegetation across at least 50% of the total terrestrial (excluding Antarctica) surface of Earth. Retention efforts could contribute to multiple goals simultaneously, especially where natural and seminatural vegetation can be managed to achieve cobenefits for biodiversity, carbon storage, and ecosystem service provision. Such management can and should co‐occur and be driven by people who live in and rely on places where natural and sustainably managed vegetation remains in situ and must be complemented by restoration and appropriate management of more human‐modified environments if global goals are to be realized.

Quantifying flood model accuracy under varying surface complexities - W. Addison-Atkinson; A.S. Chen; M. Rubinato; F.A. Memon; J.D. Shucksmith (Journal of Hydrology, 2023)

Combining UAV and Sentinel-2 satellite multi-spectral images to diagnose crop growth and N status in winter wheat at the county scale - Jie Jiang; Peter M. Atkinson; Chunsheng Chen; Qiang Cao; Yongchao Tian; Yan Zhu; Xiaojun Liu; Weixing Cao (Field Crops Research, 2023)

Pathways to achieving nature-positive and carbon–neutral land use and food systems in Wales - Sarah M. Jones; Alison C. Smith; Nicholas Leach; Peter Henrys; Peter M. Atkinson; Paula A. Harrison (Regional Environmental Change, 2023)
Land use and its management can play a vital role in carbon sequestration, but trade-offs may exist with other objectives including food security and nature recovery. Using an integrated model (the FABLE calculator), four pathways, co-created with colleagues at the Welsh Government, towards achieving climate and biodiversity targets in Wales were explored: status quo, improvements on current trends, land sparing and land sharing. We found that continuing as usual will not be sufficient to meet Wales’s climate and biodiversity targets. In contrast, the land use and agricultural sector became a net carbon sink in both the land sparing and land sharing pathways, through high afforestation targets, peatland restoration, reducing food waste and moving towards a healthier diet. Whilst both pathways released land for biodiversity, the gains were greater in the land sharing pathway, which was also less dependent on optimistic assumptions concerning productivity improvements. The results demonstrate that alternative approaches to achieving nature-positive and carbon–neutral land use and food systems may be possible, but they come with stringent and transformative requirements for policy changes, with an integrated approach necessary to maximise benefits for climate, food and nature.

Modelling and forecasting the effects of increasing sea surface temperature on coral bleaching in the Indo-Pacific region - Idham Khalil; Aidy M. Muslim; Mohammad Shawkat Hossain; Peter M. Atkinson (International Journal of Remote Sensing, 2023)

Long-term exposure to traffic-related air pollution and stroke: A systematic review and meta-analysis - P. Haddad; M. Kutlar Joss; J. Weuve; D. Vienneau; R. Atkinson; J. Brook; H. Chang; F. Forastiere; G. Hoek; R. Kappeler; F. Lurmann; S. Sagiv; et al. (International Journal of Hygiene and Environmental Health, 2023)

Associations between biomarkers of cellular senescence and physical function in humans: observations from the lifestyle interventions for elders (LIFE) study - Roger A. Fielding; Elizabeth J. Atkinson; Zaira Aversa; Thomas A. White; Amanda A. Heeren; Sara J. Achenbach; Michelle M. Mielke; Steven R. Cummings; Marco Pahor; Christiaan Leeuwenburgh; Nathan K. LeBrasseur (GeroScience, 2022)
Cellular senescence is a plausible mediator of age-associated declines in physical performance. To test this premise, we examined cross-sectional associations between circulating components of the senescence-associated secretory phenotype (SASP) and measures of physical function and muscle strength in 1377 older adults. We showed significant associations between multiple SASP proteins and the short physical performance battery (SPPB), its subcomponents (gait speed, balance, chair rise time), and 400-m walk time. Activin A, ICAM1, MMP7, VEGFA, and eotaxin showed strong associations based on gradient boost machine learning (GBM), and, when combined with other proteins, effectively identified participants at the greatest risk for mobility disability (SPPB score $$\le$$ ≤ 7). Senescence biomarkers were also associated with lower grip strength, and GBM identified PARC, ADAMTS13, and RANTES as top candidates in females, and MMP2, SOST, and MCP1 in males. These findings highlight an association between senescence biomarkers and physical performance in older adults. ClinicalTrials.gov Identifier: NCT01072500.

Rare germline variants in the AXIN2 gene in families with colonic polyposis and colorectal cancer - James M. Chan; Mark Clendenning; Sharelle Joseland; Peter Georgeson; Khalid Mahmood; Romy Walker; Julia Como; Jihoon E. Joo; Susan Preston; Ryan A. Hutchinson; Bernard J. Pope; Andrew Metz; et al. (Familial Cancer, 2022)

Infection‐competent monkeypox virus contamination identified in domestic settings following an imported case of monkeypox into the UK - Barry Atkinson; Christopher Burton; Thomas Pottage; Katy‐Anne Thompson; Didier Ngabo; Ant Crook; James Pitman; Sian Summers; Kuiama Lewandowski; Jenna Furneaux; Katherine Davies; Timothy Brooks; et al. (Environmental Microbiology, 2022)
An imported case of monkeypox was diagnosed in December 2019 in a traveller returning from Nigeria to the UK. Subsequently, environmental sampling was performed at two adjoining single‐room residences occupied by the patient and their sibling. Monkeypox virus DNA was identified in multiple locations throughout both properties, and monkeypox virus was isolated from several samples 3 days after the patient was last in these locations. Positive samples were identified following the use of both vacuum and surface sampling techniques; these methodologies allowed for environmental analysis of potentially contaminated porous and non‐porous surfaces via real‐time quantitative reverse transcriptase PCR analysis in addition to viral isolation to confirm the presence of infection‐competent virus. This report confirms the potential for infection‐competent monkeypox virus to be recovered in environmental settings associated with known positive cases and the necessity for rapid environmental assessment to reduce potential exposure to close contacts and the general public. The methods adopted in this investigation may be used for future confirmed cases of monkeypox in order to establish levels of contamination, confirm the presence of infection‐competent material and to identify locations requiring additional cleaning.

Global synthesis reveals strong multifaceted effects of eucalypts on soils - Max Mallen‐Cooper; Joe Atkinson; Zoe A. Xirocostas; Baptiste Wijas; Giancarlo M. Chiarenza; Frederick A. Dadzie; David J. Eldridge (Global Ecology and Biogeography, 2022)
Aim Eucalypts have a widespread global distribution owing to their popularity for agroforestry and as environmental plantings. Despite an abundance of site‐specific evidence that eucalypts modify soils and soil processes, we lack a quantitative synthesis of their overall effects at the global scale. This limits our capacity to assess the likely impacts of future introductions in any given region of the world. Location Global. Time period 1986–2021. Major taxa studied Eucalyptus , Angophora and Corymbia . Methods We used a systematic search to derive a database of empirical data from 227 studies across 33 countries ( n effect size = 2,806) and tested three predictions about the effects of eucalypts on soil properties and whether these effects varied with plantation age and soil depth. Results Compared with (non‐eucalypt) native vegetation, eucalypts significantly reduced soil moisture, microbial abundance, nitrogen, cations and anions. Relative reductions in soil microbes and ions were stronger in older eucalypt plantations. A comparison of eucalypts with (non‐eucalypt) silvicultural and agropastoral systems revealed similar effects on most soil properties, although eucalypts tended to reduce potassium and enhance carbon to a greater extent than other managed systems. We found no consistent effects of eucalypts on soil pH. Main conclusions Our study provides the first extensive global meta‐analysis of the effects of eucalypts on soil properties and processes and demonstrates that effects are highly dependent on the community with which they are compared (i.e., natural or managed). In general, our findings reinforce the widely held belief that eucalypts deplete soil nutrients and dominate water resources. Understanding how eucalypts affect soils allows us to assess their global suitability for agroforestry, soil rehabilitation and soil carbon enhancement, while considering the potential environmental costs.

Mismatches in scale between highly mobile marine megafauna and marine protected areas - Melinda G. Conners; Nicholas B. Sisson; Pierre D. Agamboue; Philip W. Atkinson; Alastair M. M. Baylis; Scott R. Benson; Barbara A. Block; Steven J. Bograd; Pablo Bordino; W. D. Bowen; Paul Brickle; Ignacio M. Bruno; et al. (Frontiers in Marine Science, 2022)
Marine protected areas (MPAs), particularly large MPAs, are increasing in number and size around the globe in part to facilitate the conservation of marine megafauna under the assumption that large-scale MPAs better align with vagile life histories; however, this alignment is not well established. Using a global tracking dataset from 36 species across five taxa, chosen to reflect the span of home range size in highly mobile marine megafauna, we show most MPAs are too small to encompass complete home ranges of most species. Based on size alone, 40% of existing MPAs could encompass the home ranges of the smallest ranged species, while only < 1% of existing MPAs could encompass those of the largest ranged species. Further, where home ranges and MPAs overlapped in real geographic space, MPAs encompassed < 5% of core areas used by all species. Despite most home ranges of mobile marine megafauna being much larger than existing MPAs, we demonstrate how benefits from MPAs are still likely to accrue by targeting seasonal aggregations and critical life history stages and through other management techniques.

A joint distribution framework to improve presence‐only species distribution models by exploiting opportunistic surveys - Juan M. Escamilla Molgora; Luigi Sedda; Peter Diggle; Peter M. Atkinson (Journal of Biogeography, 2022)
Aim The availability of data related to species occurrences has favoured the development of species distribution models using only observations of presence. These data are intrinsically biased by the sampling effort. Presence‐only (PO) species distribution models (SDM) typically account for this effect by introducing additional data considered to be related with the sampling. This approach, however, does not allow the characterisation of the sampling effort and hinders the interpretation of the model. Here, we propose a Bayesian framework for PO SDMs that can explicitly model the sampling effect. Location Mexico. Taxon Pines, flycatchers (family Tyranidae), birds and plants. Methods The framework defines a bivariate process separable into ecological and sampling effort processes. PO data are conceived of incomplete observations where some presences have been filtered out. A choosing principle is used to separate out presences, missing data and absences relative to the species of interest and the sampling observations. The framework provides three modelling alternatives to account for a spatial autocorrelation structure: independent latent variables (model I); common latent spatial random effect (model II) and correlated latent spatial random effects (model III). The framework was compared against the Maximum Entropy (MaxEnt) algorithm in two case studies: one for the prediction of pines and another for the prediction of flycatchers. Results In both case studies, at least one of the proposed models achieved higher predictive accuracy than MaxEnt. The model III fit best when the sampling effort was informative, while model II was more suitable in cases with a high proportion of non‐sampled sites. Main Conclusions Our approach provides a flexible framework for PO SDMs aided by a sampling effort process informed by the accumulated observations of independent and heterogeneous surveys. For the two case studies, the framework provided a model with a higher predictive accuracy than an optimised version of MaxEnt.

The Role of Satellite Telemetry Data in 21st Century Conservation of Polar Bears (Ursus maritimus) - Kristin L. Laidre; George M. Durner; Nicholas J. Lunn; Eric V. Regehr; Todd C. Atwood; Karyn D. Rode; Jon Aars; Heli Routti; Øystein Wiig; Markus Dyck; Evan S. Richardson; Stephen Atkinson; et al. (Frontiers in Marine Science, 2022)
Satellite telemetry (ST) has played a critical role in the management and conservation of polar bears ( Ursus maritimus ) over the last 50 years. ST data provide biological information relevant to subpopulation delineation, movements, habitat use, maternal denning, health, human-bear interactions, and accurate estimates of vital rates and abundance. Given that polar bears are distributed at low densities over vast and remote habitats, much of the information provided by ST data cannot be collected by other means. Obtaining ST data for polar bears requires chemical immobilization and application of a tracking device. Although immobilization has not been found to have negative effects beyond a several-day reduction in activity, over the last few decades opposition to immobilization and deployment of satellite-linked radio collars has resulted in a lack of current ST data in many of the 19 recognized polar bear subpopulations. Here, we review the uses of ST data for polar bears and evaluate its role in addressing 21 st century conservation and management challenges, which include estimation of sustainable harvest rates, understanding the impacts of climate warming, delineating critical habitat, and assessing potential anthropogenic impacts from tourism, resource development and extraction. We found that in subpopulations where ST data have been consistently collected, information was available to estimate vital rates and subpopulation density, document the effects of sea-ice loss, and inform management related to subsistence harvest and regulatory requirements. In contrast, a lack of ST data in some subpopulations resulted in increased bias and uncertainty in ecological and demographic parameters, which has a range of negative consequences. As sea-ice loss due to climate warming continues, there is a greater need to monitor polar bear distribution, habitat use, abundance, and subpopulation connectivity. We conclude that continued collection of ST data will be critically important for polar bear management and conservation in the 21 st century and that the benefits of immobilizing small numbers of individual polar bears in order to deploy ST devices significantly outweigh the risks.

Substantial long‐term loss of alpha and gamma diversity of lake invertebrates in a landscape exposed to a drying climate - S. T. Atkinson; D. Cale; A. Pinder; J. M. Chambers; S. A. Halse; Belinda J. Robson (Global Change Biology, 2021)
Many regions across the globe are shifting to more arid climates. For shallow lakes, decreasing rainfall volume and timing, changing regional wind patterns and increased evaporation rates alter water regimes so that dry periods occur more frequently and for longer. Drier conditions may affect fauna directly and indirectly through altered physicochemical conditions in lakes. Although many studies have predicted negative effects of such changes on aquatic biodiversity, empirical studies demonstrating these effects are rare. Global warming has caused severe climatic drying in southwestern Australia since the 1970s, so we aimed to determine whether lakes in this region showed impacts on lake hydroperiod, water quality, and α, β and γ diversity of lake invertebrates from 1998 to 2011. Seventeen lakes across a range of salinities were sampled biennially in spring in the Wheatbelt and Great Southern regions of Western Australia. Multivariate analyses were used to identify changes in α, β and γ diversity and examine patterns in physicochemical data. Salinity and average rainfall partially explained patterns in invertebrate richness and assemblage composition. Climatic drying was associated with significant declines in lake depth, increased frequency of dry periods, and reduced α and γ diversity (γ declined from ~300 to ~100 taxa from 1998 to 2011 in the 17 wetlands). In contrast, β diversity remained consistently high, because each lake retained a distinct fauna. Mean α diversity per‐lake declined both in lakes that dried and lakes that did not dry out, but lakes which retained a greater proportion of their maximum depth retained more α diversity. Accumulated losses in α diversity caused the decline in γ diversity likely through shrinking habitat area, fewer stepping stones for dispersal and loss of specific habitat types. Biodiversity loss is thus likely from lakes in drying regions globally. Management actions will need to sustain water depth in lakes to prevent biodiversity loss.

Advancing Social Equity in and Through Marine Conservation - Nathan J. Bennett; Laure Katz; Whitney Yadao-Evans; Gabby N. Ahmadia; Scott Atkinson; Natalie C. Ban; Neil M. Dawson; Asha de Vos; Juno Fitzpatrick; David Gill; Mael Imirizaldu; Naia Lewis; et al. (Frontiers in Marine Science, 2021)
Substantial efforts and investments are being made to increase the scale and improve the effectiveness of marine conservation globally. Though it is mandated by international law and central to conservation policy, less attention has been given to how to operationalize social equity in and through the pursuit of marine conservation. In this article, we aim to bring greater attention to this topic through reviewing how social equity can be better integrated in marine conservation policy and practice. Advancing social equity in marine conservation requires directing attention to: recognition through acknowledgment and respect for diverse peoples and perspectives; fair distribution of impacts through maximizing benefits and minimizing burdens; procedures through fostering participation in decision-making and good governance; management through championing and supporting local involvement and leadership; the environment through ensuring the efficacy of conservation actions and adequacy of management to ensure benefits to nature and people; and the structural barriers to and institutional roots of inequity in conservation. We then discuss the role of various conservation organizations in advancing social equity in marine conservation and identify the capacities these organizations need to build. We urge the marine conservation community, including governments, non-governmental organizations and donors, to commit to the pursuit of socially equitable conservation.

Chronic kidney disease of unknown origin is associated with environmental urbanisation in Belfast, UK - Jennifer M. McKinley; Ute Mueller; Peter M. Atkinson; Ulrich Ofterdinger; Siobhan F. Cox; Rory Doherty; Damian Fogarty; J. J. Egozcue; V. Pawlowsky-Glahn (Environmental Geochemistry and Health, 2021)
Chronic kidney disease (CKD), a collective term for many causes of progressive renal failure, is increasing worldwide due to ageing, obesity and diabetes. However, these factors cannot explain the many environmental clusters of renal disease that are known to occur globally. This study uses data from the UK Renal Registry (UKRR) including CKD of uncertain aetiology (CKDu) to investigate environmental factors in Belfast, UK. Urbanisation has been reported to have an increasing impact on soils. Using an urban soil geochemistry database of elemental concentrations of potentially toxic elements (PTEs), we investigated the association of the standardised incidence rates (SIRs) of both CKD and CKD of uncertain aetiology (CKDu) with environmental factors (PTEs), controlling for social deprivation. A compositional data analysis approach was used through balances (a special class of log contrasts) to identify elemental balances associated with CKDu. A statistically significant relationship was observed between CKD with the social deprivation measures of employment, income and education (significance levels of 0.001, 0.01 and 0.001, respectively), which have been used as a proxy for socio-economic factors such as smoking. Using three alternative regression methods (linear, generalised linear and Tweedie models), the elemental balances of Cr/Ni and As/Mo were found to produce the largest correlation with CKDu. Geogenic and atmospheric pollution deposition, traffic and brake wear emissions have been cited as sources for these PTEs which have been linked to kidney damage. This research, thus, sheds light on the increasing global burden of CKD and, in particular, the environmental and anthropogenic factors that may be linked to CKDu, particularly environmental PTEs linked to urbanisation.

Risk assessment of the step-by-step return-to-work policy in Beijing following the COVID-19 epidemic peak - Wen-bin Zhang; Yong Ge; Mengxiao Liu; Peter M. Atkinson; Jinfeng Wang; Xining Zhang; Zhaoxing Tian (Stochastic Environmental Research and Risk Assessment, 2021)

Filter-feeders have differential bottom-up impacts on green and brown food webs - Carla L. Atkinson; Halvor M. Halvorson; Kevin A. Kuehn; Monica Winebarger; Ansley Hamid; Matthew N. Waters (Oecologia, 2021)

Trawl fishing impacts on the status of seabed fauna in diverse regions of the globe - Tessa Mazor; C. Roland Pitcher; Wayne Rochester; Michel J. Kaiser; Jan G. Hiddink; Simon Jennings; Ricardo Amoroso; Robert A. McConnaughey; Adriaan D. Rijnsdorp; Ana M. Parma; Petri Suuronen; Jeremy Collie; et al. (Fish and Fisheries, 2021)
Bottom trawl fishing is a controversial activity. It yields about a quarter of the world's wild seafood, but also has impacts on the marine environment. Recent advances have quantified and improved understanding of large‐scale impacts of trawling on the seabed. However, such information needs to be coupled with distributions of benthic invertebrates (benthos) to assess whether these populations are being sustained under current trawling regimes. This study collated data from 13 diverse regions of the globe spanning four continents. Within each region, we combined trawl intensity distributions and predicted abundance distributions of benthos groups with impact and recovery parameters for taxonomic classes in a risk assessment model to estimate benthos status. The exposure of 220 predicted benthos‐group distributions to trawling intensity (as swept area ratio) ranged between 0% and 210% (mean = 37%) of abundance. However, benthos status, an indicator of the depleted abundance under chronic trawling pressure as a proportion of untrawled state, ranged between 0.86 and 1 (mean = 0.99), with 78% of benthos groups > 0.95. Mean benthos status was lowest in regions of Europe and Africa, and for taxonomic classes Bivalvia and Gastropoda. Our results demonstrate that while spatial overlap studies can help infer general patterns of potential risk, actual risks cannot be evaluated without using an assessment model that incorporates trawl impact and recovery metrics. These quantitative outputs are essential for sustainability assessments, and together with reference points and thresholds, can help managers ensure use of the marine environment is sustainable under the ecosystem approach to management.

Effects of the cannabinoid receptor agonist CP-55,940 on incentive salience attribution - Ali Gheidi; Lora M. Cope; Christopher J. Fitzpatrick; Benjamin N. Froehlich; Rachel Atkinson; Coltrane K. Groves; Clair N. Barcelo; Jonathan D. Morrow (Psychopharmacology, 2020)

Evolutionary history drives aspects of stoichiometric niche variation and functional effects within a guild - Carla L. Atkinson; Brian C. van Ee; John M. Pfeiffer (Ecology, 2020)
Functional traits are characteristics of an organism that represents how it interacts with its environment and can influence the structure and function of ecosystems. Ecological stoichiometry provides a framework to understand ecosystem structure and function by modeling the coupled flow of elements (e.g. carbon [C], nitrogen [N], phosphorus [P]) between consumers and their environment. Animals tend to be homeostatic in their nutrient requirements and preferentially sequester the element in shortest supply relative to demand, and release relatively more of the element in excess. Tissue stoichiometry is an important functional trait that allows for predictions among the elemental composition of animals, their diet, and their waste products, with important effects on the cycling and availability of nutrients in ecosystems. Here, we examined the tissue stoichiometric niches (C:N:P) and nutrient recycling stoichiometries (N:P) of several filter‐feeding freshwater mussels in the subfamily Ambleminae. Despite occupying the same functional‐feeding group and being restricted to a single subfamily‐level radiation, we found that species occupied distinct stoichiometric niches and that these niches varied, in part, as a function of their evolutionary history. The relationship between phylogenetic divergence and functional divergence suggests that evolutionary processes may be shaping niche complementarity and resource partitioning. Tissue and excretion stoichiometry were negatively correlated as predicted by stoichiometric theory. When scaled to the community, higher species richness and phylogenetic diversity resulted in greater functional evenness and reduced functional dispersion. Filter‐feeding bivalves are an ecologically important guild in freshwater ecosystems globally, and our study provides a more nuanced view of the stoichiometric niches and ecological functions performed by this phylogenetically and ecologically diverse assemblage.

Ensuring tests of conservation interventions build on existing literature - William J. Sutherland; Sergio Ticul Alvarez‐Castañeda; Tatsuya Amano; Roberto Ambrosini; Philip Atkinson; John M. Baxter; Alexander L. Bond; Philip J. Boon; Katherine L. Buchanan; Jos Barlow; Giuseppe Bogliani; Olivia M. Bragg; et al. (Conservation Biology, 2020)

Renewable energy development threatens many globally important biodiversity areas - Jose A. Rehbein; James E. M. Watson; Joe L. Lane; Laura J. Sonter; Oscar Venter; Scott C. Atkinson; James R. Allan (Global Change Biology, 2020)
Transitioning from fossil fuels to renewable energy is fundamental for halting anthropogenic climate change. However, renewable energy facilities can be land‐use intensive and impact conservation areas, and little attention has been given to whether the aggregated effect of energy transitions poses a substantial threat to global biodiversity. Here, we assess the extent of current and likely future renewable energy infrastructure associated with onshore wind, hydropower and solar photovoltaic generation, within three important conservation areas: protected areas (PAs), Key Biodiversity Areas (KBAs) and Earth's remaining wilderness. We identified 2,206 fully operational renewable energy facilities within the boundaries of these conservation areas, with another 922 facilities under development. Combined, these facilities span and are degrading 886 PAs, 749 KBAs and 40 distinct wilderness areas. Two trends are particularly concerning. First, while the majority of historical overlap occurs in Western Europe, the renewable electricity facilities under development increasingly overlap with conservation areas in Southeast Asia, a globally important region for biodiversity. Second, this next wave of renewable energy infrastructure represents a ~30% increase in the number of PAs and KBAs impacted and could increase the number of compromised wilderness areas by ~60%. If the world continues to rapidly transition towards renewable energy these areas will face increasing pressure to allow infrastructure expansion. Coordinated planning of renewable energy expansion and biodiversity conservation is essential to avoid conflicts that compromise their respective objectives.

A Special Issue on the Importance of Geostatistics in the Era of Data Science - Jennifer M. McKinley; Peter M. Atkinson (Mathematical Geosciences, 2020)

A Geostatistical Filter for Remote Sensing Image Enhancement - Qunming Wang; Xiaohua Tong; Peter M. Atkinson (Mathematical Geosciences, 2020)

India’s contribution to mitigating the impacts of climate change through vegetation management - J. Dash; M. D. Behera; C. Jeganathan; C. S. Jha; S. Sharma; R. Lucas; A. A. Khuroo; A. Harris; P. M. Atkinson; D. S. Boyd; C. P. Singh; M. P. Kale; et al. (Tropical Ecology, 2020)

Collective influence of household and community capitals on agricultural employment as a measure of rural poverty in the Mahanadi Delta, India - Tristan Berchoux; Gary R. Watmough; Fiifi Amoako Johnson; Craig W. Hutton; Peter M. Atkinson (Ambio, 2020)

The development of visually guided stepping - Rachel Mowbray; Janna M. Gottwald; Manfei Zhao; Anthony P. Atkinson; Dorothy Cowie (Experimental Brain Research, 2019)

Psychopathological symptoms associated with synthetic cannabinoid use: a comparison with natural cannabis - Vincent T. Mensen; Annabel Vreeker; Johan Nordgren; Amanda Atkinson; Rafael de la Torre; Magi Farré; Johannes G. Ramaekers; Tibor M. Brunt (Psychopharmacology, 2019)

Phylogeny of Mesoamerican freshwater mussels and a revised tribe‐level classification of the Ambleminae - John M. Pfeiffer; Carla L. Atkinson; Ashley E. Sharpe; Krista A. Capps; Kitty F. Emery; Lawrence M. Page (Zoologica Scripta, 2019)
Evolutionary and ecological hypotheses of the freshwater mussel subfamily Ambleminae are intensely geographically biased—a consequence of the complete exclusion of Mesoamerican taxa in phylogenetic reconstructions of the clade. We set out to integrate a portion of the Mesoamerican freshwater mussel assemblage into existing hypotheses of amblemine classification and evolution by generating a molecular phylogeny that includes four previously unsampled Mesoamerican genera and nine species endemic to that region. Given the traditionally hypothesized affinity to Nearctic mussels and the understanding that classification should reflect common ancestry, we predicted that (a) Mesoamerican genera would be recovered as members of the recognized tribes of the Ambleminae, and (b) genera would be supported as monophyletic. The mutilocus phylogeny (COI + 28S + 16S) reported herein does not fully support either of those hypotheses. Neither Cyrtonaias nor Psorula were supported as monophyletic and we predict several other Mesoamerica genera are also non‐monophyletic. The reconstructed phylogeny recovered four independent lineages of Mesoamerican freshwater mussels and these clades are distributed across the phylogeny of the Ambleminae, including the tribe Quadrulini ( Megalonaias ), Lampsilini (two lineages: Cyrtonaias explicata / Sphenonaias microdon , and Pachynaias ), and a previously unrecognized, exclusively Mesoamerican and Rio Grande clade consisting of the genera Psoronaias , Psorula and Popenaias . The latter clade possesses several morphological characteristics that distinguish it from its sister taxon, tribe Lampsilini, and we recognize this newly identified Mesoamerican clade as a fifth tribe of the Ambleminae attributable to the Popenaiadini Heard & Guckert, 1970. This revised classification more completely recognizes the suprageneric diversity of the Ambleminae.

Major trends in the land surface phenology (LSP) of Africa, controlling for land-cover change - Tracy Adole; Jadunandan Dash; Peter M. Atkinson (International Journal of Remote Sensing, 2018)

Recent shoreline evolution and beach erosion along the central Adriatic coast of Italy: the case of Molise region - Carmen M. Rosskopf; Gianluigi Di Paola; David E. Atkinson; Germán Rodríguez; Ian J. Walker (Journal of Coastal Conservation, 2018)

Large‐scale prerain vegetation green‐up across Africa - Tracy Adole; Jadunandan Dash; Peter M. Atkinson (Global Change Biology, 2018)
Information on the response of vegetation to different environmental drivers, including rainfall, forms a critical input to ecosystem models. Currently, such models are run based on parameters that, in some cases, are either assumed or lack supporting evidence (e.g., that vegetation growth across Africa is rainfall‐driven). A limited number of studies have reported that the onset of rain across Africa does not fully explain the onset of vegetation growth, for example, drawing on the observation of prerain flush effects in some parts of Africa. The spatial extent of this prerain green‐up effect, however, remains unknown, leaving a large gap in our understanding that may bias ecosystem modelling. This paper provides the most comprehensive spatial assessment to‐date of the magnitude and frequency of the different patterns of phenology response to rainfall across Africa and for different vegetation types. To define the relations between phenology and rainfall, we investigated the spatial variation in the difference, in number of days, between the start of rainy season ( SRS ) and start of vegetation growing season ( SOS ); and between the end of rainy season ( ERS ) and end of vegetation growing season ( EOS ). We reveal a much more extensive spread of prerain green‐up over Africa than previously reported, with prerain green‐up being the norm rather than the exception. We also show the relative sparsity of postrain green‐up, confined largely to the Sudano‐Sahel region. While the prerain green‐up phenomenon is well documented, its large spatial extent was not anticipated. Our results, thus, contrast with the widely held view that rainfall drives the onset and end of the vegetation growing season across Africa. Our findings point to a much more nuanced role of rainfall in Africa's vegetation growth cycle than previously thought, specifically as one of a set of several drivers, with important implications for ecosystem modelling.

Oust the louse: leaping behaviour removes sea lice from wild juvenile sockeye salmon Oncorhynchus nerka - Emma M. Atkinson; Andrew W. Bateman; Lawrence M. Dill; Martin Krkošek; John D. Reynolds; Sean C. Godwin (Journal of Fish Biology, 2018)
We conducted a manipulative field experiment to determine whether the leaping behaviour of wild juvenile sockeye salmon Oncorhynchus nerka dislodges ectoparasitic sea lice Caligus clemensi and Lepeophtheirus salmonis by comparing sea‐lice abundances between O. nerka juveniles prevented from leaping and juveniles allowed to leap at a natural frequency. Juvenile O. nerka allowed to leap had consistently fewer sea lice after the experiment than fish that were prevented from leaping. Combined with past research, these results imply potential costs due to parasitism and indicate that the leaping behaviour of juvenile O. nerka does, in fact, dislodge sea lice.

The sensitivity of breeding songbirds to changes in seasonal timing is linked to population change but cannot be directly attributed to the effects of trophic asynchrony on productivity - Samantha E. Franks; James W. Pearce‐Higgins; Sian Atkinson; James R. Bell; Marc S. Botham; Tom M. Brereton; Richard Harrington; David I. Leech (Global Change Biology, 2018)
A consequence of climate change has been an advance in the timing of seasonal events. Differences in the rate of advance between trophic levels may result in predators becoming mismatched with prey availability, reducing fitness and potentially driving population declines. Such “trophic asynchrony” is hypothesized to have contributed to recent population declines of long‐distance migratory birds in particular. Using spatially extensive survey data from 1983 to 2010 to estimate variation in spring phenology from 280 plant and insect species and the egg‐laying phenology of 21 British songbird species, we explored the effects of trophic asynchrony on avian population trends and potential underlying demographic mechanisms. Species which advanced their laying dates least over the last three decades, and were therefore at greatest risk of asynchrony, exhibited the most negative population trends. We expressed asynchrony as the annual variation in bird phenology relative to spring phenology, and related asynchrony to annual avian productivity. In warmer springs, birds were more asynchronous, but productivity was only marginally reduced; long‐distance migrants, short‐distance migrants and resident bird species all exhibited effects of similar magnitude. Long‐term population, but not productivity, declines were greatest among those species whose annual productivity was most greatly reduced by asynchrony. This suggests that population change is not mechanistically driven by the negative effects of asynchrony on productivity. The apparent effects of asynchrony on population trends are therefore either more likely to be strongly expressed via other demographic pathways, or alternatively, are a surrogate for species' sensitivity to other environmental pressures which are the ultimate cause of decline.

Mapping paddy rice fields by applying machine learning algorithms to multi-temporal Sentinel-1A and Landsat data - Alex O. Onojeghuo; George A. Blackburn; Qunming Wang; Peter M. Atkinson; Daniel Kindred; Yuxin Miao (International Journal of Remote Sensing, 2018)

NiftyPET: a High-throughput Software Platform for High Quantitative Accuracy and Precision PET Imaging and Analysis - Pawel J. Markiewicz; Matthias J. Ehrhardt; Kjell Erlandsson; Philip J. Noonan; Anna Barnes; Jonathan M. Schott; David Atkinson; Simon R. Arridge; Brian F. Hutton; Sebastien Ourselin (Neuroinformatics, 2018)

Long-term change in epibenthic assemblages at the Prince Edward Islands: a comparison between 1988 and 2013 - C. E. O. von der Meden; L. J. Atkinson; G. M. Branch; S. Asdar; I. J. Ansorge; M. van den Berg (Polar Biology, 2017)

Climate change is predicted to alter the current pest status of Globodera pallida and G. rostochiensis in the United Kingdom - Laura M. Jones; Ann‐Kristin Koehler; Mirek Trnka; Jan Balek; Andrew J. Challinor; Howard J. Atkinson; Peter E. Urwin (Global Change Biology, 2017)
The potato cyst nematodes Globodera pallida and G. rostochiensis are economically important plant pathogens causing losses to UK potato harvests estimated at £50 m/ year. Implications of climate change on their future pest status have not been fully considered. Here, we report growth of female G. pallida and G. rostochiensis over the range 15 to 25°C. Females per plant and their fecundity declined progressively with temperatures above 17.5°C for G. pallida , whilst females per plant were optimal between 17.5 and 22.5°C for G. rostochiensis . Relative reproductive success with temperature was confirmed on two potato cultivars infected with either species at 15, 22.5 and 25°C. The reduced reproductive success of G. pallida at 22.5°C relative to 15°C was also recorded for a further seven host cultivars studied. The differences in optimal temperatures for reproductive success may relate to known differences in the altitude of their regions of origin in the Andes. Exposure of G. pallida to a diurnal temperature stress for one week during female growth significantly suppressed subsequent growth for one week at 17.5°C but had no effect on G. rostochiensis . However, after two weeks of recovery, female size was not significantly different from that for the control treatment. Future soil temperatures were simulated for medium‐ and high‐emission scenarios and combined with nematode growth data to project future implications of climate change for the two species. Increased soil temperatures associated with climate change may reduce the pest status of G. pallida but benefit G. rostochiensis especially in the southern United Kingdom. We conclude that plant breeders may be able to exploit the thermal limits of G. pallida by developing potato cultivars able to grow under future warm summer conditions. Existing widely deployed resistance to G. rostochiensis is an important characteristic to retain for new potato cultivars.

Oxidative discolouration in whole-head and cut lettuce: biochemical and environmental influences on a complex phenotype and potential breeding strategies to improve shelf-life - Paul J. Hunter; Laura D. Atkinson; Laura Vickers; Stella Lignou; Maria Jose Oruna-Concha; David Pink; Paul Hand; Guy Barker; Carol Wagstaff; James M. Monaghan (Euphytica, 2017)
Lettuce discolouration is a key post-harvest trait. The major enzyme controlling oxidative discolouration has long been considered to be polyphenol oxidase (PPO) however, levels of PPO and subsequent development of discolouration symptoms have not always correlated. The predominance of a latent state of the enzyme in plant tissues combined with substrate activation and contemporaneous suicide inactivation mechanisms are considered as potential explanations for this phenomenon. Leaf tissue physical properties have been associated with subsequent discolouration and these may be influenced by variation in nutrient availability, especially excess nitrogen and head maturity at harvest. Mild calcium and irrigation stress has also been associated with a reduction in subsequent discolouration, although excess irrigation has been linked to increased discolouration potentially through leaf physical properties. These environmental factors, including high temperature and UV light intensities, often have impacts on levels of phenolic compounds linking the environmental responses to the biochemistry of the PPO pathway. Breeding strategies targeting the PAL and PPO pathway biochemistry and environmental response genes are discussed as a more cost-effective method of mitigating oxidative discolouration then either modified atmosphere packaging or post-harvest treatments, although current understanding of the biochemistry means that such programs are likely to be limited in nature and it is likely that they will need to be deployed alongside other methods for the foreseeable future.

Ontogenetic body‐mass scaling of nitrogen excretion relates to body surface area in diverse pelagic invertebrates - A. G. Hirst; M. K. S. Lilley; D. S. Glazier; D. Atkinson (Limnology and Oceanography, 2017)
Many physiological and ecological processes depend on body size and the supply of limiting nutrients. Hence, it is important to derive quantitative predictions based on a mechanistic understanding of the influence of body size on metabolic rate and on the ratios of consumed to excreted elements. Among diverse pelagic invertebrates that change shape during ontogeny, recent analysis has demonstrated a significant positive correlation between the body‐mass allometry of respiration rates (measured as the ontogenetic body mass‐scaling exponent b R ) and the allometry of body surface area ( b A , as predicted from body‐shape changes using a Euclidean model). As many pelagic invertebrates use a large portion of their external body surface for both resource uptake and waste excretion, we predicted that body‐mass scaling exponents for rates of excretion of soluble N ( b N ) should also then relate to the degree of body‐shape change during growth. We tested this hypothesis using literature data on b N for 39 species of pelagic invertebrates across five different phyla, and find strong support: b N is significantly positively correlated with predicted b A , whilst also co‐varying with b R . Intraspecific differences between b N and b R values reveal ontogenetic shifts in the ratio of O 2 ‐consumed to N‐excreted. We suggest that a variety of factors, including adaptive developmental shifts in the relative anabolism and catabolism of proteins and lipids, may cause these shifts in consumption–excretion ratios. Diverse pelagic invertebrates that dominate vast open water ecosystems falsify the predictions of general metabolic scaling theories built upon resource‐transport networks, but support predictions of surface‐area dependent theory.

Reference Intervals of Mineral Elements in Plasma of Anesthetized Free-Ranging Adult Females of South American Sea Lion, Otaria flavescens - Paula S. Polizzi; L. N. Chiodi Boudet; A. Ponce de León; M. Quiroga; D. H. Rodríguez; S. Atkinson; M. S. Gerpe (Biological Trace Element Research, 2016)

A multiple-point spatially weighted k -NN classifier for remote sensing - Yunwei Tang; Linhai Jing; Peter M. Atkinson; Hui Li (International Journal of Remote Sensing, 2016)

Seasonal nutritional status in Norway lobsters, Nephrops norvegicus (L.): are females nutritionally compromised over the winter? - Andrew J. R. Watts; Amaya Albalat; Ian P. Smith; Robert J. A. Atkinson; Douglas M. Neil (Marine Biology Research, 2016)

Epidemiological risk factors associated with inflammatory breast cancer subtypes - Rachel L. Atkinson; Randa El-Zein; Vicente Valero; Anthony Lucci; Therese B. Bevers; Tamer Fouad; Weiqin Liao; Naoto T. Ueno; Wendy A. Woodward; Abenaa M. Brewster (Cancer Causes & Control, 2016)

Seismically induced landslide hazard and exposure modelling in Southern California based on the 1994 Northridge, California earthquake event - M. E. A. Budimir; P. M. Atkinson; H. G. Lewis (Landslides, 2015)

Magnitude Estimation for the 2011 Tohoku-Oki Earthquake Based on Ground Motion Prediction Equations - Attieh Eshaghi; Kristy F. Tiampo; Hadi Ghofrani; Gail M. Atkinson (Pure and Applied Geophysics, 2015)

Crop rotational diversity enhances belowground communities and functions in an agroecosystem - L. K. Tiemann; A. S. Grandy; E. E. Atkinson; E. Marin‐Spiotta; M. D. McDaniel (Ecology Letters, 2015)
Biodiversity loss, an important consequence of agricultural intensification, can lead to reductions in agroecosystem functions and services. Increasing crop diversity through rotation may alleviate these negative consequences by restoring positive aboveground–belowground interactions. Positive impacts of aboveground biodiversity on belowground communities and processes have primarily been observed in natural systems. Here, we test for the effects of increased diversity in an agroecosystem, where plant diversity is increased over time through crop rotation. As crop diversity increased from one to five species, distinct soil microbial communities were related to increases in soil aggregation, organic carbon, total nitrogen, microbial activity and decreases in the carbon‐to‐nitrogen acquiring enzyme activity ratio. This study indicates positive biodiversity–function relationships in agroecosystems, driven by interactions between rotational and microbial diversity. By increasing the quantity, quality and chemical diversity of residues, high diversity rotations can sustain soil biological communities, with positive effects on soil organic matter and soil fertility.

Erratum to: Earthquake-and-landslide events are associated with more fatalities than earthquakes alone - M. E. A. Budimir; P. M. Atkinson; H. G. Lewis (Natural Hazards, 2015)

A systematic review of landslide probability mapping using logistic regression - M. E. A. Budimir; P. M. Atkinson; H. G. Lewis (Landslides, 2015)

A novel multi-parameter support vector machine for image classification - Ce Zhang; Tiejun Wang; Peter M. Atkinson; Xin Pan; Huapeng Li (International Journal of Remote Sensing, 2015)

Elucidating the impact of temperature variability and extremes on cereal croplands through remote sensing - John M. A. Duncan; Jadunandan Dash; Peter M. Atkinson (Global Change Biology, 2015)
Remote sensing‐derived wheat crop yield‐climate models were developed to highlight the impact of temperature variation during thermo‐sensitive periods (anthesis and grain‐filling; TSP ) of wheat crop development. Specific questions addressed are: can the impact of temperature variation occurring during the TSP on wheat crop yield be detected using remote sensing data and what is the impact? Do crop critical temperature thresholds during TSP exist in real world cropping landscapes? These questions are tested in one of the world's major wheat breadbaskets of Punjab and Haryana, north‐west India. Warming average minimum temperatures during the TSP had a greater negative impact on wheat crop yield than warming maximum temperatures. Warming minimum and maximum temperatures during the TSP explain a greater amount of variation in wheat crop yield than average growing season temperature. In complex real world cereal croplands there was a variable yield response to critical temperature threshold exceedance, specifically a more pronounced negative impact on wheat yield with increased warming events above 35 °C. The negative impact of warming increases with a later start‐of‐season suggesting earlier sowing can reduce wheat crop exposure harmful temperatures. However, even earlier sown wheat experienced temperature‐induced yield losses, which, when viewed in the context of projected warming up to 2100 indicates adaptive responses should focus on increasing wheat tolerance to heat. This study shows it is possible to capture the impacts of temperature variation during the TSP on wheat crop yield in real world cropping landscapes using remote sensing data; this has important implications for monitoring the impact of climate change, variation and heat extremes on wheat croplands.

Duration of the 2011 Tohoku earthquake ground motions - Hadi Ghofrani; Gail M. Atkinson (Journal of Seismology, 2015)

From animal cage to aircraft cabin: an overview of evidence translation in jet lag research - Greg Atkinson; Alan M. Batterham; Nigel Dowdall; Andrew Thompson; Alwin van Drongelen (European Journal of Applied Physiology, 2014)

Associations between daily mortality in London and combined oxidant capacity, ozone and nitrogen dioxide - M. L. Williams; R. W. Atkinson; H. R. Anderson; F. J. Kelly (Air Quality, Atmosphere & Health, 2014)

What is the impact of systematically missing exposure data on air pollution health effect estimates? - Evangelia Samoli; Roger D. Peng; Tim Ramsay; Giota Touloumi; Francesca Dominici; Richard W. Atkinson; Antonella Zanobetti; Alain Le Tertre; H. Ross Anderson; Joel Schwartz; Aaron Cohen; Daniel Krewski; et al. (Air Quality, Atmosphere & Health, 2014)

Accounting for the Impact of Conservation on Human Well‐Being - E.J. MILNER‐GULLAND; J.A. MCGREGOR; M. AGARWALA; G. ATKINSON; P. BEVAN; T. CLEMENTS; T. DAW; K. HOMEWOOD; N. KUMPEL; J. LEWIS; S. MOURATO; B. PALMER FRY; et al. (Conservation Biology, 2014)
Conservationists are increasingly engaging with the concept of human well‐being to improve the design and evaluation of their interventions. Since the convening of the influential Sarkozy Commission in 2009, development researchers have been refining conceptualizations and frameworks to understand and measure human well‐being and are starting to converge on a common understanding of how best to do this. In conservation, the term human well‐being is in widespread use, but there is a need for guidance on operationalizing it to measure the impacts of conservation interventions on people. We present a framework for understanding human well‐being, which could be particularly useful in conservation. The framework includes 3 conditions; meeting needs, pursuing goals, and experiencing a satisfactory quality of life. We outline some of the complexities involved in evaluating the well‐being effects of conservation interventions, with the understanding that well‐being varies between people and over time and with the priorities of the evaluator. Key challenges for research into the well‐being impacts of conservation interventions include the need to build up a collection of case studies so as to draw out generalizable lessons; harness the potential of modern technology to support well‐being research; and contextualize evaluations of conservation impacts on well‐being spatially and temporally within the wider landscape of social change. Pathways through the smog of confusion around the term well‐being exist, and existing frameworks such as the Well‐being in Developing Countries approach can help conservationists negotiate the challenges of operationalizing the concept. Conservationists have the opportunity to benefit from the recent flurry of research in the development field so as to carry out more nuanced and locally relevant evaluations of the effects of their interventions on human well‐being. Consideración del Impacto de la Conservación sobre el Bienestar Humano

Effects of two contrasting canopy manipulations on growth and water use of London plane (Platanus x acerifolia) trees - Neil A. Hipps; Michael J. Davies; Joel M. Dunn; Howard Griffiths; Christopher J. Atkinson (Plant and Soil, 2014)

Uncertainty in recurrence rates of large magnitude events due to short historic catalogs - Tariq Mohammed; Gail M. Atkinson; Karen Assatourians (Journal of Seismology, 2014)

Earthquake-and-landslide events are associated with more fatalities than earthquakes alone - M. E. A. Budimir; P. M. Atkinson; H. G. Lewis (Natural Hazards, 2014)

HIV-associated distal neuropathic pain is associated with smaller total cerebral cortical gray matter - John R. Keltner; Christine Fennema-Notestine; Florin Vaida; Dongzhe Wang; Donald R. Franklin; Robert H. Dworkin; Chelsea Sanders; J. Allen McCutchan; Sarah L. Archibald; David J. Miller; George Kesidis; Clint Cushman; et al. (Journal of NeuroVirology, 2014)

Pierre Dutilleul: Spatio-temporal Heterogeneity: Concepts and Analyses - Peter M. Atkinson (Mathematical Geosciences, 2014)

Exploring the spatio-temporal relationship between two key aeroallergens and meteorological variables in the United Kingdom - Nabaz Khwarahm; Jadunandan Dash; Peter M. Atkinson; R. M. Newnham; C. A. Skjøth; B. Adams-Groom; Eric Caulton; K. Head (International Journal of Biometeorology, 2014)

Ground-motion prediction equations for interface earthquakes of M7 to M9 based on empirical data from Japan - Hadi Ghofrani; Gail M. Atkinson (Bulletin of Earthquake Engineering, 2014)

Developing Marine Protected Area Networks in the Coral Triangle: Good Practices for Expanding the Coral Triangle Marine Protected Area System - Rebecca Weeks; Porfirio M. Aliño; Scott Atkinson; Pacifico Beldia; Augustine Binson; Wilfredo L. Campos; Rili Djohani; Alison L. Green; Richard Hamilton; Vera Horigue; Robecca Jumin; Kay Kalim; et al. (Coastal Management, 2014)

Blood pressure regulation VII. The “morning surge” in blood pressure: measurement issues and clinical significance - Greg Atkinson; Alan M. Batterham; Kazuomi Kario; Chloe E. Taylor; Helen Jones (European Journal of Applied Physiology, 2014)

Erratum to: Dissolved inorganic carbon and total alkalinity of a Hawaiian fringing reef: chemical techniques for monitoring the effects of ocean acidification on coral reefs - C. A. Lantz; M. J. Atkinson; C. W. Winn; S. E. Kahng (Coral Reefs, 2014)

Dissolved inorganic carbon and total alkalinity of a Hawaiian fringing reef: chemical techniques for monitoring the effects of ocean acidification on coral reefs - C. A. Lantz; M. J. Atkinson; C. W. Winn; S. E. Kahng (Coral Reefs, 2014)

Retraction Note: Patterns of bee diversity in mosaic agricultural landscapes of central Uganda: implication of pollination services conservation for food security - M. B. Théodore Munyuli; Philip Nyeko; Simon Potts; Phil Atkinson; Derek Pomeroy; Juliet Vickery (Journal of Insect Conservation, 2014)

Ecological sustainability in rangelands: the contribution of remote sensing - Tal Svoray; Avi Perevolotsky; Peter M. Atkinson (International Journal of Remote Sensing, 2013)

Identification of a possible respiratory arsenate reductase in Denitrovibrio acetiphilus, a member of the phylum Deferribacteres - Kyle Denton; Morgan M. Atkinson; Stacey P. Borenstein; Alexis Carlson; Thomas Carroll; Kristen Cullity; Casey DeMarsico; Daniel Ellowitz; Andrea Gialtouridis; Rachel Gore; April Herleikson; Albee Yun Ling; et al. (Archives of Microbiology, 2013)

Acute effects of ambient ozone on mortality in Europe and North America: results from the APHENA study - Roger D. Peng; Evangelia Samoli; Luu Pham; Francesca Dominici; Giota Touloumi; Tim Ramsay; Richard T. Burnett; Daniel Krewski; Alain Le Tertre; Aaron Cohen; Richard W. Atkinson; H. Ross Anderson; et al. (Air Quality, Atmosphere & Health, 2013)

Conformation and stability properties of B17: II. Analytical investigations using differential scanning calorimetry - Hassan M. Khachfe; David Atkinson (European Biophysics Journal, 2013)

Development and Preliminary Evaluation of a Training Workshop for the Collection of Patient-Reported Outcome (PRO) Interview Data by Research Support Staff - Thomas M. Atkinson; Karen Hurley; Carma L. Bylund; Alexandra Berk; Kimberly Diminni; Jamie S. Ostroff (Journal of Cancer Education, 2013)

Analysing temporal trends in the Indian Summer Monsoon and its variability at a fine spatial resolution - J. M. A. Duncan; J. Dash; P. M. Atkinson (Climatic Change, 2013)

Environmental changes impacting Echinococcus transmission: research to support predictive surveillance and control - Jo‐An M. Atkinson; Darren J. Gray; Archie C.A. Clements; Tamsin S. Barnes; Donald P. McManus; Yu R. Yang (Global Change Biology, 2013)
Echinococcosis, resulting from infection with tapeworms Echinococcus granulosus and E. multilocularis, has a global distribution with 2–3 million people affected and 200,000 new cases diagnosed annually. Costs of treatment for humans and economic losses to the livestock industry have been estimated to exceed $2 billion. These figures are likely to be an underestimation given the challenges with its early detection and the lack of mandatory official reporting policies in most countries. Despite this global burden, echinococcosis remains a neglected zoonosis. The importance of environmental factors in influencing the transmission intensity and distribution of Echinococcus spp. is increasingly being recognized. With the advent of climate change and the influence of global population expansion, food insecurity and land‐use changes, questions about the potential impact of changing temperature, rainfall patterns, increasing urbanization, deforestation, grassland degradation and overgrazing on zoonotic disease transmission are being raised. This study is the first to comprehensively review how climate change and anthropogenic environmental factors contribute to the transmission of echinococcosis mediated by changes in animal population dynamics, spatial overlap of competent hosts and the creation of improved conditions for egg survival. We advocate rigorous scientific research to establish the causal link between specific environmental variables and echinococcosis in humans and the incorporation of environmental, animal and human data collection within a sentinel site surveillance network that will complement satellite remote‐sensing information. Identifying the environmental determinants of transmission risk to humans will be vital for the design of more accurate predictive models to guide cost‐effective pre‐emptive public health action against echinococcosis.

RETRACTED ARTICLE: Patterns of bee diversity in mosaic agricultural landscapes of central Uganda: implication of pollination services conservation for food security - M. B. Théodore Munyuli; Philip Nyeko; Simon Potts; Phil Atkinson; Derek Pomeroy; Juliet Vickery (Journal of Insect Conservation, 2013)

Implications of the 2011 M9.0 Tohoku Japan earthquake for the treatment of site effects in large earthquakes - Hadi Ghofrani; Gail M. Atkinson; Katsuichiro Goda (Bulletin of Earthquake Engineering, 2013)

An enzyme activity capable of endotransglycosylation of heteroxylan polysaccharides is present in plant primary cell walls - Sarah L. Johnston; Roneel Prakash; Nancy J. Chen; Monto H. Kumagai; Helen M. Turano; Janine M. Cooney; Ross G. Atkinson; Robert E. Paull; Roshan Cheetamun; Antony Bacic; David A. Brummell; Roswitha Schröder (Planta, 2013)

Influence of Tyrphostin AG490 on the expression of diabetes-associated markers in human adipocytes - Abdoreza Davoodi-Semiromi; C. H. Wasserfall; A. Hassanzadeh; R. M. Cooper-DeHoff; M. Wabitsch; M. Atkinson (Immunogenetics, 2013)

Conformation and stability properties of B17: I. Analytical investigations using circular dichroism - Hassan M. Khachfe; David Atkinson (European Biophysics Journal, 2012)

Super-resolution mapping using Hopfield Neural Network with panchromatic imagery - Quang Minh Nguyen; Peter M. Atkinson; Hugh G. Lewis (International Journal of Remote Sensing, 2011)

Integrated catchment management—interweaving social process and science knowledge - A Fenemor; C Phillips; W Allen; RG Young; G Harmsworth; B Bowden; L Basher; PA Gillespie; M Kilvington; R Davies‐Colley; J Dymond; A Cole; et al. (New Zealand Journal of Marine and Freshwater Research, 2011)
This paper provides an overview of the Motueka integrated catchment management (ICM) research programme. This research was based on the thesis that achieving ecosystem resilience at a catchment scale requires active measures to develop community resilience. We define a generic adaptive planning and action process, with associated knowledge management and stakeholder involvement processes, and illustrate those processes with observations from five research themes: (1) water allocation; (2) land use effects on water; (3) land and freshwater impacts on the coast; (4) integrative tools and processes for managing cumulative effects; and (5) building human capital and facilitating community action. Our research clearly illustrates the benefits for effective decision‐making of carrying out catchment scale science and management within collaborative processes which patiently develop trusting relationships. We conclude that coastal catchments should be managed as a holistic continuum from ridge tops to the sea and that some processes like floods or loss of community resilience have decadal consequences, which support the need for long‐term monitoring and investment.

Creative platforms for social learning in ICM: the Watershed Talk project - M Kilvington; M Atkinson; A Fenemor (New Zealand Journal of Marine and Freshwater Research, 2011)
Watershed Talk was an action research project within the Motueka‐based integrated catchment management research programme. It explored processes of dialogue between catchment residents, scientists and resource managers, and examined how design of creative processes can shift people's understanding and develop their capacity to address the complex environmental issues that they face. The project was highly reflective, and examined the potential transformative power of constructive conversation and the means by which social learning platforms can affect the legacy of skills, knowledge and enthusiasm for action amongst participants. Three important elements for the design of platforms for social learning were identified: (1) the value of using principles to guide process design; (2) the potential outcomes from using creative approaches to generate dialogue; and (3) the importance of integrating evaluation and reflection into platform design to both manage the platform and to help cement new learning amongst participants. This paper outlines the fundamental aspects of the Watershed Talk platform design, its implementation, and conclusions drawn from evaluation of the experience.

A characterisation of climate variability and trends in hydrological extremes in the Severn Uplands - Eloise M. Biggs; Peter M. Atkinson (International Journal of Climatology, 2011)
Hydrological and climatic characteristics were investigated within the Severn Uplands to determine the interconnection between variables with a focus on understanding changes in hydrological extremes. Time series of precipitation and flows over a 30‐year period were analysed for trends in extremes. The Mann–Kendall (MK) non‐parametric test was used to detect trends at six rain gauges and five flow gauges across the catchment. Maxima, percentiles and N ‐day maxima of precipitation and flow distributions were investigated to identify changes in extreme intensity, frequency and persistence, respectively. Results indicated some significant statistical trends at annual, seasonal, and monthly scales. The largest number of significant trends in extreme precipitation was identified at mountainous gauge locations where significant increases in extreme precipitation persistence were detected annually and during spring and winter. Additionally, significant increases in extreme precipitation frequency were observed annually and during autumn and winter. Trends in flow identified an increase in extreme intensity on an annual basis, as well as during winter and the month of July, and a decrease in extreme frequency at certain stations during spring. Changes in climate variables were investigated to identify causal relationships with precipitation and flow hydrological extremes. Extremes were found to coincide with certain weather types, generally characteristic of cyclonic conditions and/or orographic enhancement. These were largely correlated with strong positive and negative stages of the North Atlantic oscillation, particularly during winter. Snow cover records indicated rapid decline in the Severn Uplands and a reduction in snow indicated a link to changes in spring hydrological extremes. All changes seemed to be driven by the underlying climate variable of air temperature, which coincided with changes in observed national and global temperature records. Hydroclimatological changes indicated a possible temporal shift in the occurrence of extreme hydrological events, which was likely to have been affected by changes in catchment physical properties. Copyright © 2010 Royal Meteorological Society

Seabed foraging by Antarctic krill: Implications for stock assessment, bentho‐pelagic coupling, and the vertical transfer of iron - Katrin Schmidt; Angus Atkinson; Sebastian Steigenberger; Sophie Fielding; Margaret C. M. Lindsay; David W. Pond; Geraint A. Tarling; Thor A. Klevjer; Claire S. Allen; Stephen Nicol; Eric P. Achterberg (Limnology and Oceanography, 2011)
A compilation of more than 30 studies shows that adult Antarctic krill ( Euphausia superba ) may frequent benthic habitats year‐round, in shelf as well as oceanic waters and throughout their circumpolar range. Net and acoustic data from the Scotia Sea show that in summer 2‐20% of the population reside at depths between 200 and 2000 m, and that large aggregations can form above the seabed. Local differences in the vertical distribution of krill indicate that reduced feeding success in surface waters, either due to predator encounter or food shortage, might initiate such deep migrations and results in benthic feeding. Fatty acid and microscopic analyses of stomach content confirm two different foraging habitats for Antarctic krill: the upper ocean, where fresh phytoplankton is the main food source, and deeper water or the seabed, where detritus and copepods are consumed. Krill caught in upper waters retain signals of benthic feeding, suggesting frequent and dynamic exchange between surface and seabed. Krill contained up to 260 nmol iron per stomach when returning from seabed feeding. About 5% of this iron is labile, i.e., potentially available to phytoplankton. Due to their large biomass, frequent benthic feeding, and acidic digestion of particulate iron, krill might facilitate an input of new iron to Southern Ocean surface waters. Deep migrations and foraging at the seabed are significant parts of krill ecology, and the vertical fluxes involved in this behavior are important for the coupling of benthic and pelagic food webs and their elemental repositories.

CNP budgets of a coral-dominated fringing reef at La Réunion, France: coupling of oceanic phosphate and groundwater nitrate - P. Cuet; M. J. Atkinson; J. Blanchot; B. E. Casareto; E. Cordier; J. Falter; P. Frouin; H. Fujimura; C. Pierret; Y. Susuki; C. Tourrand (Coral Reefs, 2011)

Water velocity dependence of phosphate uptake on a coral-dominated fringing reef flat, La Réunion Island, Indian Ocean - P. Cuet; C. Pierret; E. Cordier; M. J. Atkinson (Coral Reefs, 2011)

The Why, What, and How of Global Biodiversity Indicators Beyond the 2010 Target - JULIA P. G. JONES; BEN COLLEN; GILES ATKINSON; PETER W. J. BAXTER; PHILIP BUBB; JANINE B. ILLIAN; TODD E. KATZNER; AIDAN KEANE; JONATHAN LOH; EVE MCDONALD‐MADDEN; EMILY NICHOLSON; HENRIQUE M. PEREIRA; et al. (Conservation Biology, 2011)
The 2010 biodiversity target agreed by signatories to the Convention on Biological Diversity directed the attention of conservation professionals toward the development of indicators with which to measure changes in biological diversity at the global scale. We considered why global biodiversity indicators are needed, what characteristics successful global indicators have, and how existing indicators perform. Because monitoring could absorb a large proportion of funds available for conservation, we believe indicators should be linked explicitly to monitoring objectives and decisions about which monitoring schemes deserve funding should be informed by predictions of the value of such schemes to decision making. We suggest that raising awareness among the public and policy makers, auditing management actions, and informing policy choices are the most important global monitoring objectives. Using four well‐developed indicators of biological diversity (extent of forests, coverage of protected areas, Living Planet Index, Red List Index) as examples, we analyzed the characteristics needed for indicators to meet these objectives. We recommend that conservation professionals improve on existing indicators by eliminating spatial biases in data availability, fill gaps in information about ecosystems other than forests, and improve understanding of the way indicators respond to policy changes. Monitoring is not an end in itself, and we believe it is vital that the ultimate objectives of global monitoring of biological diversity inform development of new indicators.

Exploring the impact of climate and land use changes on streamflow trends in a monsoon catchment - Nor Aizam Adnan; Peter M. Atkinson (International Journal of Climatology, 2011)
Flooding appears to be increasing in Kelantan, Malaysia, in terms of frequency as well as magnitude. This is likely to be due to changes in precipitation, but may also be contributed to by land use change. The Mann–Kendall non‐parametric method was used to test for trends in streamflow and precipitation at the 90% significance level. Several significant trends in streamflow were found for the upstream (River Galas) and downstream (River Kelantan) sub‐catchments for all variables (annual, seasonal and monthly time‐series). In particular, streamflow increased in all seasons in the upstream sub‐catchment, but increased in the wet season and decreased in the dry season downstream. Several trends were also observed for precipitation. Precipitation trends were increasing in the wet season and decreasing in the dry season for both upstream and downstream sub‐catchments. Analysis of land use change revealed that most changes occurred through conversion of forest to agricultural land (i.e. rubber and oil palm), predominantly in the upstream sub‐catchment. The analysis suggests a clear association between streamflow change and precipitation change, but also reveals that land use change may be an important contributing factor, particularly in the upstream sub‐catchment. Copyright © 2010 Royal Meteorological Society

Short-term coherency between gross primary production and community respiration in an algal-dominated reef flat - J. L. Falter; M. J. Atkinson; D. W. Schar; R. J. Lowe; S. G. Monismith (Coral Reefs, 2011)

HIV-associated neurocognitive disorders before and during the era of combination antiretroviral therapy: differences in rates, nature, and predictors - Robert K. Heaton; Donald R. Franklin; Ronald J. Ellis; J. Allen McCutchan; Scott L. Letendre; Shannon LeBlanc; Stephanie H. Corkran; Nichole A. Duarte; David B. Clifford; Steven P. Woods; Ann C. Collier; Christina M. Marra; et al. (Journal of NeuroVirology, 2011)

Neurocognitive functioning in acute or early HIV infection - David J. Moore; Scott L. Letendre; Sheldon Morris; Anya Umlauf; Reena Deutsch; Davey M. Smith; Susan Little; Alexandra Rooney; Donald R. Franklin; Ben Gouaux; Shannon LeBlanc; Debra Rosario; et al. (Journal of NeuroVirology, 2011)

Environmental Factors Affecting Ultraviolet Photodegradation Rates and Estrogenicity of Estrone and Ethinylestradiol in Natural Waters - Susanna K. Atkinson; Vicki L. Marlatt; Lynda E. Kimpe; David R. S. Lean; Vance L. Trudeau; Jules M. Blais (Archives of Environmental Contamination and Toxicology, 2011)

Mapping the phenology of natural vegetation in India using a remote sensing-derived chlorophyll index - C. Jeganathan; J. Dash; P. M. Atkinson (International Journal of Remote Sensing, 2010)

Cadmium, Copper, Iron, and Zinc Concentrations in Kidneys of Grey Wolves, Canis lupus, from Alaska, Idaho, Montana (USA) and the Northwest Territories (Canada) - S. R. Hoffmann; S. A. Blunck; K. N. Petersen; E. M. Jones; J. C. Koval; R. Misek; J. A. Frick; H. D. Cluff; C. A. Sime; M. McNay; K. B. Beckman; M. W. Atkinson; et al. (Bulletin of Environmental Contamination and Toxicology, 2010)

On the seasonal cycles and variability of Florida Straits, Ekman and Sverdrup transports at 26° N in the Atlantic Ocean - C. P. Atkinson; H. L. Bryden; J. J-M. Hirschi; T. Kanzow (Ocean Science, 2010)
Since April 2004 the RAPID array has made continuous measurements of the Atlantic Meridional Overturning Circulation (AMOC) at 26° N. Two key components of this system are Ekman transport zonally integrated across 26° N and western boundary current transport in the Florida Straits. Whilst measurements of the AMOC as a whole are somewhat in their infancy, this study investigates what useful information can be extracted on the variability of the Ekman and Florida Straits transports using the decadal timeseries already available. Analysis is also presented for Sverdrup transports zonally integrated across 26° N. The seasonal cycles of Florida Straits, Ekman and Sverdrup transports are quantified at 26° N using harmonic analysis of annual and semi-annual constituents. Whilst Sverdrup transport shows clear semi-annual periodicity, calculations of seasonal Florida Straits and Ekman transports show substantial interannual variability due to contamination by variability at non-seasonal frequencies; the mean seasonal cycle for these transports only emerges from decadal length observations. The Florida Straits and Ekman mean seasonal cycles project on the AMOC with a combined peak-to-peak seasonal range of 3.5 Sv. The combined seasonal range for heat transport is 0.40 PW. The Florida Straits seasonal cycle possesses a smooth annual periodicity in contrast with previous studies suggesting a more asymmetric structure. No clear evidence is found to support significant changes in the Florida Straits seasonal cycle at sub-decadal periods. Whilst evidence of wind driven Florida Straits transport variability is seen at sub-seasonal and annual periods, a model run from the 1/4° eddy-permitting ocean model NEMO is used to identify an important contribution from internal oceanic variability at sub-annual and interannual periods. The Ekman transport seasonal cycle possesses less symmetric structure, due in part to different seasonal transport regimes east and west of 50 to 60° W. Around 60% of non-seasonal Ekman transport variability occurs in phase section-wide at 26° N and is related to the NAO, whilst Sverdrup transport variability is more difficult to decompose.

Biocontrol potential of an endophytic Serratia sp. G3 and its mode of action - X. Liu; J. Jia; S. Atkinson; M. Cámara; K. Gao; H. Li; J. Cao (World Journal of Microbiology and Biotechnology, 2010)

Coseismic stress parameter of three California Earthquakes derived from the stochastic finite fault technique - Karen Assatourians; Gail M. Atkinson (Journal of Seismology, 2010)

Utilizing image texture to detect land-cover change in Mediterranean coastal wetlands - S. Berberoğlu; A. Akin; P. M. Atkinson; P. J. Curran (International Journal of Remote Sensing, 2010)

Effects of alcohol preload on attentional bias towards cocaine-related cues - Catharine Montgomery; Matt Field; Amanda M. Atkinson; Jon C. Cole; Andrew J. Goudie; Harry R. Sumnall (Psychopharmacology, 2010)

The influence of defined ante-mortem stressors on the early post-mortem biochemical processes in the abdominal muscle of the Norway lobster, Nephrops norvegicus (Linnaeus, 1758) - Sebastian G. Gornik; Amaya Albalat; Robert J. A. Atkinson; Graham H. Coombs; Douglas M. Neil (Marine Biology Research, 2010)

Applying the HAZUS-MH software tool to assess seismic risk in downtown Ottawa, Canada - S. K. Ploeger; G. M. Atkinson; C. Samson (Natural Hazards, 2010)

Optimisation of contained Nicotiana tabacum cultivation for the production of recombinant protein pharmaceuticals - Richard Colgan; Christopher J. Atkinson; Matthew Paul; Sally Hassan; Pascal M. W. Drake; Amy L. Sexton; Simon Santa-Cruz; David James; Keith Hamp; Colin Gutteridge; Julian K-C. Ma (Transgenic Research, 2010)

Myxobolus notropis from emerald shiner, Notropis atherinoides Rafinesque, in Lake Superior - D Horner; S D Atkinson; D M Pratt; S Marcquenski; J L Bartholomew (Journal of Fish Diseases, 2010)

Geostatistically estimated image noise is a function of variance in the underlying signal - A. Asmat; P. M. Atkinson; G. M. Foody (International Journal of Remote Sensing, 2010)

Microphthalmia, parkinsonism, and enhanced nociception in Pitx3 416insG mice - Michael Rosemann; Alesia Ivashkevich; Jack Favor; Claudia Dalke; Sabine M. Hölter; Lore Becker; Ildikó Rácz; Ines Bolle; Martina Klempt; Birgit Rathkolb; Svetoslav Kalaydjiev; Thure Adler; et al. (Mammalian Genome, 2010)

Coral disease following massive bleaching in 2005 causes 60% decline in coral cover on reefs in the US Virgin Islands - J. Miller; E. Muller; C. Rogers; R. Waara; A. Atkinson; K. R. T. Whelan; M. Patterson; B. Witcher (Coral Reefs, 2009)

Issues of uncertainty in super-resolution mapping and their implications for the design of an inter-comparison study - Peter M. Atkinson (International Journal of Remote Sensing, 2009)

Effect of capture method on the physiology and nucleotide breakdown products in the Norway lobster ( Nephrops norvegicus ) - Amaya Albalat; Sebastian G. Gornik; Robert J. A. Atkinson; Graham H. Coombs; Douglas M. Neil (Marine Biology Research, 2009)

Associations between endogenous sex hormone levels and mammographic and bone densities in premenopausal women - Mellissa Yong; Charlotte Atkinson; Katherine M. Newton; Erin J. Aiello Bowles; Frank Z. Stanczyk; Kim C. Westerlind; Victoria L. Holt; Stephen M. Schwartz; Wendy M. Leisenring; Johanna W. Lampe (Cancer Causes & Control, 2009)

Mapping percentage tree cover from Envisat MERIS data using linear and nonlinear techniques - S. Berberoglu; O. Satir; P. M. Atkinson (International Journal of Remote Sensing, 2009)

Production of transgenic pineapple (Ananas cosmos (L.) Merr.) plants via adventitious bud regeneration - M.-L. Wang; G. Uruu; L. Xiong; X. He; C. Nagai; K. T. Cheah; J. S. Hu; G.-L. Nan; B. S. Sipes; H. J. Atkinson; P. H. Moore; K. G. Rohrbach; et al. (In Vitro Cellular & Developmental Biology - Plant, 2009)

Estimating per‐pixel thematic uncertainty in remote sensing classifications - K. M. Brown; G. M. Foody; P. M. Atkinson (International Journal of Remote Sensing, 2009)

Irrigation scheduling and irrigation systems: optimising irrigation efficiency for container ornamental shrubs - Olga M. Grant; Michael J. Davies; Helen Longbottom; Christopher J. Atkinson (Irrigation Science, 2009)

Daidzein-metabolizing phenotypes in relation to serum hormones and sex hormone binding globulin, and urinary estrogen metabolites in premenopausal women in the United States - Charlotte Atkinson; Katherine M. Newton; Frank Z. Stanczyk; Kim C. Westerlind; Lin Li; Johanna W. Lampe (Cancer Causes & Control, 2008)

Coral reef benthic productivity based on optical absorptance and light-use efficiency - E. J. Hochberg; M. J. Atkinson (Coral Reefs, 2008)

Renal myxozoanosis in weedy sea dragons, Phyllopteryx taeniolatus (Lacepède), caused by Sinuolinea phyllopteryxa n. sp. - M M Garner; S D Atkinson; S L Hallett; J L Bartholomew; R W Nordhausen; H Reed; L Adams; B Whitaker (Journal of Fish Diseases, 2008)
Renal myxozoanosis was diagnosed histologically in 11 captive, wild caught, adult weedy (common) sea dragons, Phyllopteryx taeniolatus , from three separate public aquaria in the United States. Myxozoan spores were visible in wet mounts of kidney tissue and were associated with renal tubular dilatation and tubular epithelial cell hypertrophy. Light and electron microscopy revealed spore morphology consistent with the genus Sinuolinea . Spores were spheroidal, slightly dorso‐ventrally compressed, length ( L ) 17.1 × width ( W ) 16.4 × thickness ( T ) 15.6 μm, with two shell valves joined at a distinct, sinuous sutural ridge, and had two nearly spherical polar capsules, L 5.5 × W 5.0 μm, with five to seven turns of the polar filament. There were no extra‐valvular ridges or protrusions. DNA sequencing required the design of three new primers that yielded 1740 bp of 18S ribosomal DNA sequence. The parasite was determined to be novel based on morphological and molecular data, and was given the name Sinuolinea phyllopteryxa after its vertebrate host.

Unusual new Chaetosphaeria species from New Zealand: Intrafamilial diversity and elucidations of the Chaetosphaeriaceae ‐Lasiosphaeriaceae relationship (Sordariomycetes, Ascomycotina) - Toni J. Atkinson; Andrew N. Miller; Sabine M. Huhndorf; David A. Orlovich (New Zealand Journal of Botany, 2007)
Chaetosphaeria albida, C. bombycina , and C. metallicans are described and compared with other Chaetosphaeria taxa using morphological and molecular methods. The fresh ascomata of C. albida are almost white, translucent, and aereolate; they are papillate with a distinctive 4‐layered peridium, and the ascospores are scolecosporous, multiseptate, and hyaline. C. bombycina is similar, but the fresh ascomata are light fawn‐grey with a reflective silken appearance, non‐papillate, and the similar peridium is 3‐layered. C. metallicans has ascomata which are blue‐black, shiny and metallic when fresh; the thick peridium is heavily melanised, and the ascospores are straight to allantoid, 3‐septate, and hyaline. The scolecosporous ascospores of C. albida and C. bombycina would have traditionally referred these taxa to Lasiosphaeria . However, like C. metallicans , they lack a peridial tomentum, and have asci with light‐refractive, non‐amyloid apical rings, without a sub‐apical globule. Despite the major differences in spore shape and ascomal wall structure, analyses of the LSU and ITS regions of ribosomal DNA suggest that genetically all three fall within Chaetosphaeria , near to C. raciborskii , and in a sister clade to the type species C. innumera . The placement of these species considerably expands current morphological conceptions of Chaetosphaeria , particularly in terms of ascomal wall appearance and structure, and confirms the existence of a scolecosporous group within the genus. in the search for morphological characters which mimic genetic relationships, this study further elucidates the relationship between the Chaetosphaeriaceae and the Lasiosphaeriaceae.

Enhancing Drug Development and Drug Monitoring: Academia, Industry and Government Chart Common Goals - Walter Wolf; Dennis J. Atkinson; Patrick M. Colletti (Pharmaceutical Research, 2007)

Detection of iodine monoxide radicals in the marine boundary layer using laser induced fluorescence spectroscopy - Lisa K. Whalley; Kate L. Furneaux; Tom Gravestock; Helen M. Atkinson; Catherine S. E. Bale; Trevor Ingham; William J. Bloss; Dwayne E. Heard (Journal of Atmospheric Chemistry, 2007)

Effects of water velocity on picoplankton uptake by coral reef communities - M. Ribes; M. J. Atkinson (Coral Reefs, 2007)

Modelling geometric and misregistration error in airborne sensor data to enhance change detection - K. M. Brown; G. M. Foody; P. M. Atkinson (International Journal of Remote Sensing, 2007)

Alloparenting in Steller sea lions (Eumetopias jubatus): correlations with misdirected care and other observations - John M. Maniscalco; Karin R. Harris; Shannon Atkinson; Pamela Parker (Journal of Ethology, 2007)

Idiopathic muscle necrosis in the Norway lobster, Nephrops norvegicus (L.): aetiology, pathology and progression to bacteraemia - I D Ridgway; G D Stentiford; A C Taylor; R J A Atkinson; T H Birkbeck; D M Neil (Journal of Fish Diseases, 2007)
The pathology and progression of idiopathic muscle necrosis (IMN) in Nephrops norvegicus and possible aetiologies have been investigated. Trawl capture, aerial exposure and handling initiate IMN, and the condition can be induced through periods of aerial exposure alone, in the absence of trawling. Within 24–48 h after trawl capture IMN progresses to a multi‐species bacterial septicaemia, with moribund animals exhibiting clinical signs. The aetiology of this condition has been examined using molecular (16S rRNA gene sequencing) and biochemical (standard taxonomic assays, Biolog TM ) criteria to characterize bacterial isolates from moribund and healthy animals. Histopathology of the IMN phase reveals a loss of sarcomeric structure with necrotic lesions containing pyknotic nuclei, fragments of myofibrils and connective tissue elements. In the bacterial phase there is extensive loss of abdominal muscle structure, and the presence of rod‐shaped Gram‐negative bacteria in the degrading tissues. The results demonstrate that the IMN condition is connected to stressful conditions imposed on N. norvegicus , but involves no pathogenic agents. This is followed by an opportunistic bacterial infection that causes further tissue spoilage. It is believed that the primary cause of both IMN and bacteraemia is imposed stress, but they are expressed in different time courses.

ASSESSING KILLER WHALE PREDATION ON STELLER SEA LIONS FROM FIELD OBSERVATIONS IN KENAI FJORDS, ALASKA - John M. Maniscalco; Craig O. Matkin; Daniela Maldini; Donald G. Calkins; Shannon Atkinson (Marine Mammal Science, 2007)
The behavioral and predatory patterns of Gulf of Alaska (GOA) transient killer whales ( Orcinus orca ) were studied between 2000 and 2005 using remote video and vessel‐based observations near the Chiswell Island Steller sea lion ( Eumetopias jubatus ) rookery and in the broader Kenai Fjords (KF) region of the northern GOA. GOA transient killer whales were observed on 118 d over the 6‐yr period; the median group size was two (range: 1–9). Nine predation events were observed from vessels and an additional sixteen were inferred from remote video studies; all involved Steller sea lions. Estimates from field observations suggest that fifty‐nine sea lions were consumed over the summer seasons of 2002–2005; whereas estimates based on published caloric requirements of transient killer whales would suggest a loss of 103 sea lions over the same time period. GOA transients spent a large proportion (43%) of their time resting which may be a strategy for conserving energy. Predation on sea lion pups at the Chiswell Island rookery was greatest during years when a single killer whale was foraging alone and when a 1.5‐yr‐old calf was evidently being trained to handle prey. Predation on pups was low during years when killer whales were foraging in groups and were observed and presumed to be taking mostly juvenile sea lions. Our study suggests that GOA transients are having a minor effect on the recovery of Steller sea lions in the GOA.

Effects of elevated p CO 2 on epilithic and endolithic metabolism of reef carbonates - TRIBOLLET ALINE; M. J. ATKINSON; LANGDON CHRISTOPHER (Global Change Biology, 2006)
We investigated effects of elevated partial pressure of CO 2 ( p CO 2 ) on the metabolism of epilithic and endolithic phototrophic communities that colonized experimental coral blocks. Blocks of the massive coral Porites lobata were exposed to colonization by epilithic and endolithic organisms at an oceanic site in Kaneohe Bay (Hawaii) for 6 months, and then were transported to laboratory tanks. A bubbling system was used to maintain two treatments for 3 months, one at ambient p CO 2 (400 ppm) and the second at elevated p CO 2 (750 ppm). Net photosynthetic rates of epilithic communities in the high p CO 2 treatment, dominated by encrusting coralline algae, decreased by 35% while respiration rates remained constant. In contrast, metabolism of endolithic phototrophs, comprised of cyanobacteria and algae, was not significantly affected by the elevated p CO 2 even though endoliths contributed about 63% to block production.

Bio-optical modeling of photosynthetic pigments in corals - Eric J. Hochberg; Amy M. Apprill; Marlin J. Atkinson; Robert R. Bidigare (Coral Reefs, 2006)

Pre-maturity α-amylase and incipient sprouting in UK winter wheat, with special reference to the variety Rialto - A. F. Tjin Wong Joe; R. W. Summers; G. D. Lunn; M. D. Atkinson; P. S. Kettlewell (Euphytica, 2005)

SUMO wrestling with type 1 diabetes - Manyu Li; Dehuang Guo; Carlos M. Isales; Decio L. Eizirik; Mark Atkinson; Jin-Xiong She; Cong-Yi Wang (Journal of Molecular Medicine, 2005)

Spatial variability of factors influencing coastal change in the Western Canadian Arctic - G. K. Manson; S. M. Solomon; D. L. Forbes; D. E. Atkinson; M. Craymer (Geo-Marine Letters, 2005)

Arctic Coastal Dynamics (ACD): an introduction - Volker Rachold; Feliks E. Are; David E. Atkinson; Georgy Cherkashov; Steven M. Solomon (Geo-Marine Letters, 2005)

Simulated Climatology of Atmospheric Ducts Over the Persian Gulf - M. Zhu; B. W. Atkinson (Boundary-Layer Meteorology, 2005)

Observed and modelled climatology of the land–sea breeze circulation over the Persian Gulf - M. Zhu; B. W. Atkinson (International Journal of Climatology, 2004)
A combination of observations and a numerical model revealed the meso‐scale structure of the near‐surface atmospheric conditions over the Persian Gulf. Low‐level winds were dominated by a single, coherent, perennial land–sea breeze circulation (LSBC) that varied seasonally and diurnally. In summer the sea breeze was deeper and wider than in winter. At night the core of the LSBC over the Gulf was confluent with uplift, whereas in daytime it was difluent with subsidence. Sensitivity tests with the model revealed the influence on the LSBC of the land–sea distribution, orography and the ambient wind. The latter resulted in different conditions over the north, east, south and west coasts. Over the north coast, where the opposing ambient wind created a sea breeze front, landward penetration was very limited; over the south coast it was over 250 km. The thermal effect of the Iranian mountains accentuated the depth and penetration, landward and seaward, of the LSBC, thus influencing the duration of the land and sea breezes over the east coast. From spring to autumn the marine boundary layer over the Gulf was shallow, cool, moist and stable, with strong vertical gradients of temperature and humidity at its top. Its depth increased in the ambient flow from northwest to southeast and also, in daytime, from west to east, because of different magnitudes of the subsidence in the sea breeze circulation over the west and east coasts. Copyright © 2004 Royal Meteorological Society

Habitat selection in whiting - C. J. L. Atkinson; M. Bergmann; M. J. Kaiser (Journal of Fish Biology, 2004)
Given a choice of habitats in a laboratory experiment, whiting Merlangius merlangus preferentially spent most time over sand, then gravel and least time over a habitat with emergent structures. The introduction of a predator stimulus increased the preference for the sand habitat for large whiting, whereas small whiting had an increased preference for the habitat with emergent structures.

Relationships between airborne fungal spore concentration of Cladosporium and the summer climate at two sites in Britain - P. D. Hollins; P. S. Kettlewell; D. B. Stephenson; J. M. Corden; W. M. Millington; J. Mullins; M. D. Atkinson (International Journal of Biometeorology, 2004)

A media-based assessment of damage and ground motions from the january 26th, 2001M 7.6 Bhuj, India earthquake - Susan E Hough; Stacey Martin; Roger Bilham; Gail M Atkinson (Journal of Earth System Science, 2003)

Nutrient uptake by coral-reef microatolls - A. D. L. Steven; M. J. Atkinson (Coral Reefs, 2003)

Kinetics and Products of the Gas-Phase Reaction of OH Radicals with 5-Hydroxy-2-Pentanone at 296± 2 K - Sara M. Aschmann; Janet Arey; Roger Atkinson (Journal of Atmospheric Chemistry, 2003)

Molecular characterisation of two aurantiactinomyxon (Myxozoa) phenotypes reveals one genotype - S L Hallett; S D Atkinson; M El‐Matbouli (Journal of Fish Diseases, 2002)

Response to the comment by G. Symonds, K.P. Black, and I.R. Young on "A physical derivation of nutrient-uptake rates in coral reefs: effects of roughness and waves - C. Hearn; M. Atkinson; J. Falter (Coral Reefs, 2002)

Directing Research to Reduce the Impacts of Nonindigenous Species - James E. Byers; Sarah Reichard; John M. Randall; Ingrid M. Parker; Carey S. Smith; W. M. Lonsdale; I. A. E. Atkinson; T. R. Seastedt; Mark Williamson; E. Chornesky; D. Hayes (Conservation Biology, 2002)
Management of nonindigenous species is a crucial aspect of maintaining native biodiversity and normal ecosystem functions. We attempt to guide researchers in developing projects that will be of use to conservation practitioners, tangibly improving applied conservation measures. We advocate a directed approach for conservation research to aid in prioritizing nonindigenous species for intervention by resource managers. This approach includes outlining what needs to be known to make such relative judgments about the impacts of nonindigenous species and the most promising methods by which to obtain such information. We also address active measures that should be taken once priorities have been set, highlighting the roles of risk assessment and research in improving control efforts. Ultimately, a better match between research and practical conservation needs should result in more effective reduction of the effects of nonindigenous species on native species.

Effects of a hydroxy-cinnamoyl conjugate of spermidine on arthropod neuromuscular junctions - Klose M.; Atkinson J.; Mercier A. (Journal of Comparative Physiology A, 2002)

Nutrient dynamics in the Biosphere 2 coral reef mesocosm: water velocity controls NH4 and PO4 uptake - M. Atkinson; J. Falter; C. Hearn (Coral Reefs, 2001)

A physical derivation of nutrient-uptake rates in coral reefs: effects of roughness and waves - C. Hearn; M. Atkinson; J. Falter (Coral Reefs, 2001)

Production‐respiration relationships at different timescales within the Biosphere 2 coral reef biome - James L. Falter; M. J. Atkinson; Chris Langdon (Limnology and Oceanography, 2001)
Temporal relationships between organic carbon production and respiration are not well understood in coral reef ecosystems. We monitored dissolved oxygen (O 2 ) concentrations within the Biosphere 2 coral reef biome over a 3‐yr period (1 January 1997–1 January 2000), to calculate daily rates of gross production (P), community respiration (R), and net community production (NCP). P averaged 170 mmol O 2 m −2 d −1 , and R averaged 173 mmol O 2 m −2 d −1 , which yielded a mean NCP of only ‐3 mmol O 2 m22 d21, or a difference of only 2%. This long‐term balance between P and R reflects the closed‐system design of the biome. The SD of P, however, was ±56 mmol O 2 m −2 d −1 ; that of R was ±47 mmol O 2 m −2 d −1 ; and that of NCP was ±26 mmol O 2 m −2 d −1 or ±15% of mean P. To better resolve the behavior of P, R, and NCP at different timescales, each of these time series were spectrally decomposed into four frequency bands that corresponded to four timescales: 3 months (seasonal to annual). At timescales >1 month, the variance of P was not different from the variance of R. At timescales of

Ammonium regeneration by Antarctic mesozooplankton: an allometric approach - Atkinson A.; Whitehouse M. (Marine Biology, 2001)

Uptake of estrone from the water column by a coral community - Tarrant A.; Atkinson M.; Atkinson S. (Marine Biology, 2001)

Spectral discrimination of coral reef benthic communities - E. J. Hochberg; M. J. Atkinson (Coral Reefs, 2000)

Polygalacturonase gene expression in kiwifruit: relationship to fruit softening and ethylene production - Zhong-Yan Wang; Elspeth A. MacRae; Michele A. Wright; Karen M. Bolitho; Gavin S. Ross; Ross G. Atkinson (Plant Molecular Biology, 2000)

Evaluating perturbations and developing restoration strategies for inland wetlands in the Great Lakes basin - Naomi E. Detenbeck; Susan M. Galatowitsch; Jim Atkinson; Helen Ball (Wetlands, 1999)

Drought tolerance of apple rootstocks: Production and partitioning of dry matter - Christopher J. Atkinson; Michaelangelo Policarpo; Anthony D. Webster; Ayzin M. Kuden (Plant and Soil, 1999)

Evaluation of the Best disease gene in patients with age-related macular degeneration and other maculopathies - R. Allikmets; Johanna M. Seddon; Paul S. Bernstein; A. Hutchinson; Andrew Atkinson; Sanjay Sharma; Bernard Gerrard; W. Li; Michael L. Metzker; Claes Wadelius; C. Thomas Caskey; Michael Dean; et al. (Human Genetics, 1999)

Transgenic Arabidopsis leaf tissue expressing a modified oryzacystatin shows resistance to the field slug Deroceras reticulatum (Müller) - Anthony J. Walker; Peter E. Urwin; Howard J. Atkinson; Philip Brain; David M. Glen; Peter R. Shewry (Transgenic Research, 1999)

Apple ACC-oxidase and polygalacturonase: ripening-specific gene expression and promoter analysis in transgenic tomato - Ross G. Atkinson; Karen M. Bolitho; Michele A. Wright; Teresa Iturriagagoitia-Bueno; Suzanne J. Reid; Gavin S. Ross (Plant Molecular Biology, 1998)

An integrated genetic linkage map of the laboratory rat - Donna M. Brown *, , Tara C. Matise; George Koike; Jason S. Simon; Eric S. Winer; Sarah Zangen; Michael G. McLaughlin; Masahide Shiozawa; O. Scott Atkinson; James R. Hudson, Jr.; Aravinda Chakravarti; Eric S. Lander **, , Howard (Mammalian Genome, 1998)

GUS expression patterns from a tobacco yellow dwarf virus-based episomal vector - P. D. Needham; R. G. Atkinson; B. A. M. Morris; R. C. Gardner; A. P. Gleave (Plant Cell Reports, 1998)

Expression of an engineered cysteine proteinase inhibitor (Oryzacystatin-IΔD86) for nematode resistance in transgenic rice plants - P. Vain; B. Worland; M. C. Clarke; G. Richard; M. Beavis; H. Liu; A. Kohli; M. Leech; J. Snape; P. Christou; H. Atkinson (Theoretical and Applied Genetics, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Radiometric dating of the Middle Palaeolithic tool industry and associated fauna of Pin Hole Cave, Creswell Crags, England - Roger M. Jacobi; Peter J. Rowe; Mabs A. Gilmour; Rainer Grün; Timothy C. Atkinson (Journal of Quaternary Science, 1998)

Measurement and prediction of mass transfer to experimental coral reef communities - M. E. Baird; M. J. Atkinson (Limnology and Oceanography, 1997)
The uptake of nutrients (N and P) into coral reef communities is proposed to be limited by diffusion through concentration‐depleted boundary layers between the water and organisms, or what is termed “mass transfer limitation.” The mass transfer rate is a physical limit to the rate of nutrient uptake. Maximum uptake rates by highly rough biological surfaces have not yet been evaluated. Engineering correlations indicate that increased surface roughness should increase mass transfer, although it has been difficult to quantify roughness of living corals. In this paper, the effects of highly rough coral surfaces on mass transfer were investigated by using dissolution of gypsum (plaster‐of‐paris) from flat smooth surfaces and coral skeletons. The gypsum dissolution rates were measured as an increase in concentration of calcium ions in freshwater recirculating over experimental surfaces. Stanton numbers (St m , a dimensionless number giving the ratio of uptake rate per unit area to the rate of advection of the substance past the uptake surface) of experimental smooth surfaces ranged from 2.6 to 3.5 × 10 −5 and were the same as values in the engineering literature for smooth surfaces. St m for coral‐shaped surfaces ranged from 70 × 10 −5 at 0.03 m s −1 to 17 × 10 −5 at velocities up to 0.50 m s −1 and were in general 9 ± 1 times that of smooth surfaces. The measured St m for each coral‐shaped surface was the same as the predicted St m (±10%) calculated from measured friction and roughness using a correlation of heat transfer. St m for ammonia uptake on living coral reef communities show the same relationship between mass transfer, friction, and roughness as the coral‐shaped gypsum surfaces. The transport rates of nutrients to reef surfaces are controlled by large‐scale roughness, typically associated with coral heads, and not small‐scale roughness elements on the organisms, nor biological alterations of diffusive boundary layers. Nutrient uptake and possibly other metabolic exchange rates arc governed by concentration, water velocity, and friction dissipated over the reef, denoting that coral reef community metabolism is physically forced.

A LARGE PLACENTA ENCOUNTERED IN THE HAWAIIAN WINTER GROUNDS OF THE HUMPBACK WHALE, MEGAPTERA NOVAEANGLIAE - L. E. Silvers; S. Atkinson; M. Iwasa; C. Combelles; D. R. Salden (Marine Mammal Science, 1997)

Biochemical composition of Nephrops norvegicus : changes associated with ovary maturation - I. D. Tuck; A. C. Taylor; R. J. A. Atkinson; M. E. Gramitto; C. Smith (Marine Biology, 1997)

Structure and grazing impact of the mesozooplankton community during late summer 1994 near South Georgia, Antarctica - E. A. Pakhomov; H. M. Verheye; A. Atkinson; R. K. Laubscher; J. Taunton-Clark (Polar Biology, 1997)

LIPOFUSCIN GRANULAR CELLS IN REGRESSING CORPORA LUTEA AND CORPORA ALBICANTIA OF OVARIES FROM WILD HAWAIIAN MONK SEALS ( MONACHUS SCHAUINSLANDI ) - M. IWASA; S. ATKINSON; S. KAMIYA (Marine Mammal Science, 1997)

In situ hybridization in Actinidia using repeat DNA and genomic probes - G. Yan; R. G. Atkinson; A. R. Ferguson; M. A. McNeilage; B. G. Murray (Theoretical and Applied Genetics, 1997)

Ammonium uptake by coral reefs: Effects of water velocity and surface roughness on mass transfer - F. I. M. Thomas; M. J. Atkinson (Limnology and Oceanography, 1997)
To test the hypothesis that ammonium uptake by coral reefs is mass‐transfer limited and to determine the relative effects of water velocity and community roughness on uptake, we measured the rates of ammonium uptake by reefs at velocities ranging from 3.3 to 37.5 cm s ‒1 . Two assemblages of coral rubble (relatively rough and relatively smooth) and two assemblages of live coral ( Porites compressa and Pocillopora damicornis ) were used. Rate constants for uptake ranged from 16 to 144 × 10 ‒6 m ‒1 , and were positively correlated to water velocity. We estimated roughness of each assemblage as mean height, relief, and by measuring the friction coefficient of each assemblage at water velocities ranging from 3.3 to 58.0 cm s ‒1 . Friction coefficients ranged from 0.033 to 0.264. Stanton numbers (a dimensionless ratio of uptake rate to advection past the uptake surface) calculated from experimental data were within 80% of those calculated from empirically derived engineering equations describing heat transfer to rough surfaces. Results support the hypothesis that ammonium uptake is mass‐transfer limited and are consistent with mass transfer relationships for nonbiotic surfaces.

Isolation, identification and characterisation of a soil bacterium producing an enzyme with l-phenylalanine oxidase activity - G. M. Brearley; C. P. Price; T. Atkinson; P. M. Hammond (Archives of Microbiology, 1994)

Isolation, identification and characterisation of a soil bacterium producing an enzyme with l-phenylalanine oxidase activity - G. M. Brearley; C. P. Price; T. Atkinson; P. M. Hammond (Archives of Microbiology, 1994)

Kinetics of the atmospherically important gas-phase reactions of a series of trimethyl phosphorothioates - Mark A. Goodman; Sara M. Aschmann; Roger Atkinson; Arthur M. Winer (Archives of Environmental Contamination and Toxicology, 1988)

Atmospheric gas phase loss processes for chlorobenzene, benzotrifluoride, and 4-chlorobenzotrifluoride, and generalization of predictive techniques for atmospheric lifetimes of aromatic compounds - Roger Atkinson; Sara M. Aschmann; Arthur M. Winer; James N. Pitts (Archives of Environmental Contamination and Toxicology, 1985)

A study of the atmospheric reactions of 1,3-dichloropropene and other selected organochlorine compounds - Ernesto C. Tuazon; Roger Atkinson; Arthur M. Winer; James N. Pitts (Archives of Environmental Contamination and Toxicology, 1984)